Degradation of mycotoxins in cow milk by dielectric barrier discharge cold plasma and its effect on milk quality - Yike Han; Shangchen Fu; Meng Li; Siqi Wang; Yijie Lu; Wupeng Ge; Chunfeng Guo; Yuan Zhou; Zhenpeng Gao (International Dairy Journal, 2026)

Integrating habitat connectivity and fishing pressure to promote migratory marine species conservation - Guodong Li; Cuicui Feng; Haibin Han; Xinyun Ge; Rongliang Zhang; Fangping Cheng; Xin Fang; Han Dong; Chang Liu; Wei Huang; Jiangning Zeng (Reviews in Fish Biology and Fisheries, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Preparation of coal gasification coarse slag-based low-carbon cementitious materials based on supersulfated cement system: matching mechanism between reaction path induced by multi-mineral salts and mechanical properties - Xiaowei Ge; Xiaowei Gu; Ziyang Hu; Shenyu Wang; Xu Wang; Shaoqian Liu; Xuecheng Ding; Jinchi Han; Jianping Liu; Hao Wang; Xuemei Liu (Chemical Engineering Journal, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Novel dual-functional depressant for the selective depression behavior and mechanism of fluorite and calcite in bastnaesite flotation - Ruiqi Ge; Wenbao Liu; Yonglun Wang; Bohan Wang; Wengang Liu; Sikai Zhao; Cong Han; Yanbai Shen (Minerals Engineering, 2026)

Bench-scale proof-of-concept evaluation of whole-cell quorum quenching for fouling mitigation in a constant-flux membrane bioreactor. - Jiale Han; Xiaohui Chen; Xiaoyu Wang; Zimiao Yan; Xinjiao Dong; Yaru Li; Chenjie Mei; Shimei Ge (Journal of Water Process Engineering, 2026)

Enhanced ability of Nano-Fe3O4- immobilized Serratia sp. Z4 in mitigating membrane biofouling in a membrane bioreactor system during wastewater treatment - Shimei Ge; Zaoxia Zhao; Yaru Li; Jiale Han; Panpan Liu; Xinjiao Dong (Journal of Environmental Chemical Engineering, 2026)

Boron and nitrogen co-doped carbon dots for fructose sensing: selective visual readout and machine learning-assisted semi-quantification - Yingying Li; Tingli Liu; Kai Jia; Yiming Gou; Han Xu; Chunhua Ge; Xiangdong Zhang (Food Chemistry, 2026)

Adaptive seasonal management after eradicating invasive Spartina: A nature-based approach - Dong-Fan Xu; Qi Yuan; Hai-Qiang Guo; Bing Tan; Fei Quan; Zhe-Xiu Yu; Dong-Yang Han; Yu-Jiao Lu; Ying-Ying Hao; Si-Qi Zhou; Guang Ge; Bin Zhao; et al. (Ecological Engineering, 2026)

Construction of porous liquids based on carbon coated hierarchically porous TS-1 particles and deep eutectic solvents for SO2 selective separation - Shuaiyong Dou; Mengru Sun; Yameng Zhao; Yuheng Zhen; Xiaofei Du; Ao Zhang; Cunchao Yang; Guoquan Liu; Shixuan Wu; Meixuan Ge; Aibin Kang; Erhong Duan; et al. (Chemical Engineering Journal, 2026)

A konjac glucomannan-based hydrogel delivery system induces trained immunity via enhanced oxidative phosphorylation for improved vaccine protection - Zheng Jia; Yadong Gao; Husile Han; Chaonan Wang; Jiaqing Wang; Junjie Guo; Shuhe Zhang; Yifan Li; Junwei Ge; Fang Wang; Mingchun Gao (Carbohydrate Polymers, 2026)

Numerical investigation of straight-line navigation motion response of the under-water vehicle under irregular waves - Guo Wang; Junbo Ge; JingJing Zhang; Yunxiang You; Panpan Han (Ocean Engineering, 2026)

Microplastics disrupt bacterial defense within the plant–AMF–bacteria continuum to amplify Cd bioavailability - Xiaohui Han; Yuxuan Gao; Jixin Chen; Peng Yang; Xinran Liang; Lei Wang; Yu Ge; Heng Gui; Yongmei He; Fangdong Zhan; Xinhou Zhang; Yakov Kuzyakov (Journal of Hazardous Materials, 2026)

Preference-guided land-use optimization and trade-off coordination under different development goals from a township zoning perspective: A case study of rural Qiqihar, China - Yujin Zhou; Ge Liu; Kaishan Song; Shidi Shao; Yang Li; Bingqian Han; Jipeng Zhang (Journal of Cleaner Production, 2026)

Unveiling the molecular interplay: phosvitin as a stabilizer of lactoferrin against thermal denaturation - Ling Zhang; Wenduo Han; Han Sun; Wenqi Ge; Jiawen Pei; Jiajing Liu; Shubo Luo; Xiang Duan; Xuebo Liu (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

Multi-stage energy absorption of 3D hollow auxetic metamaterials at extremely low relative density - Dong Han; Zhongli Ge; Pengfei Li; Puhao Li; Peng Wang; Fan Yang (Engineering Structures, 2026)

Curdlan-mangiferin composite hydrogel encapsulating coenzyme Q10 alleviates dry eye disease by improving mitochondrial function - Wenshuo Han; Yaning Liu; Huanhuan Ge; Hanwen Guo; Xinqi Zhao; Zijian Gao; Guohu Di; Xianggen Wu; Lei Tian; Peng Chen; Xiaoping Zhang (Chemical Engineering Journal, 2026)

Substrate-mediated spatial cooperation in Bacillus-Saccharomyces consortia enhance starch hydrolysis and flavor formation during solid-state fermentation - Liming Wu; Yitong Ge; Zichang Peng; Zinuan Han; Jiaqi Bai; Ting Lan; Zhenchao Zhang; Fuhao Liang; Xiaole Xia (Bioresource Technology, 2026)

SCAD-DTA: spherical concept alignment with dynamic multi-modal fusion for drug–target affinity prediction - Zhensong Wang; Weiliang Han; Ge Kong; Yuan Zhang; Jiajie Xing; Juan Wang (Molecular Diversity, 2026)

A bidirectional spatiotemporal cross-domain fusion model for TSM retrieval in inland waters - Chen Wang; Huimin Lu; Ge Liu; Dongmei Lü; Shizhuo Liu; Bingqian Han; Yang Li; Kaishan Song (Journal of Oceanology and Limnology, 2026)

A Sea Surface Salinity error correction model integrating physical models and complex environmental influences - Yanling Han; Wenbin Zhao; Qinqin Sun; Ge Song; Ping Ma; Yun Zhang; Chuanxiang Hua; Shouqi Cao (International Journal of Remote Sensing, 2026)

Erratum to “Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning” [Toxicology and Applied Pharmacology 516 (2026) 117995] - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

Retraction notice to “Physicochemically protected organic carbon release is the rate-limiting step of rhizosphere priming in paddy soils” [Sci. Total Environ. 955 (2024) 176859] - Cuiyan Wu; Wei Huang; Yixian Liu; Han Li; Shuai Ding; Zhenke Zhu; Feng Wang; Feike A. Dijkstra; Guangbin Zhang; Yakov Kuzyakov; Weiguo Cheng; Mouliang Xiao; et al. (Science of The Total Environment, 2026)

Quantifying facility-scale CO2 emissions using spaceborne hyperspectral imageries - Ge Han; Huayi Wang; Zhipeng Pei; Huiqin Mao; Jiaying Ying; Siwei Li; Xin Ma; Boming Liu; Feiyue Mao; Wei Gong (Remote Sensing of Environment, 2026)

Predefined-time global prescribed performance tracking of ASV via adaptive event-triggered control - Peng Chen; Tao Han; Bo Xiao; Yuan Tan; Xi-Sheng Zhan; Ming-Feng Ge (Ocean Engineering, 2026)

The paradox of rural depopulation and built-up growth: Insights from two decades of settlement change in China (2000–2020) - Yujin Zhou; Jipeng Zhang; Ge Liu; Kaishan Song; Bingxue Zhu; Sijia Li; Shidi Shao; Yang Li; Bingqian Han (Land Use Policy, 2026)

Trace volatile sulfur compounds in biogases from sanitary landfill site: emission level, toxicity, and mitigation measure - Tong Gao; Jinlong Li; Lin Li; Yanjie Wang; Jingyun Ge; Yunping Han (Journal of Cleaner Production, 2026)

Polystyrene microplastics trigger intestinal inflammation through CXCL11-mediated T-cell recruitment - Yao Tan; Xiaoyan Chen; Hao Ge; Yu Han; Binqi Yang; Xiaopeng Zhu; Li Yuan (Journal of Environmental Sciences, 2026)

CO2 phase state controls multiscale water displacement in a deep bituminous coal - Jing Han; Zhe Zhou; Zhaolong Ge; Changzheng Lu; Jiaqi Wei (International Journal of Rock Mechanics and Mining Sciences, 2026)

Exploring the endogenous and exogenous key aroma-active components in three aroma types of black teas from different cultivars - Weixuan Li; Zhouling Zhong; Han Yan; Longyu Guo; Ge Chen; Zhi Lin; Haipeng Lv; Yue Zhang; Yin Zhu (Food Research International, 2026)

MgO-modified PtSn/Ce-DMSN as an efficient catalyst for oxidative dehydrogenation of propane with carbon dioxide - Chao Peng; Jiang Li; Han-Qing Ge; Meng Yan; Zhong-Wen Liu (Chemical Engineering Journal, 2026)

Differences between human and rat 5α-Reductase 1 inhibition by phenolic disinfectants: Comparative kinetics and binding modes for neurosteroid synthesis - Xinyu Han; Wanyu Li; Yinghao Huang; Lisha Wang; Tianchi Zhao; Xishi Chen; Hao Lin; Yiyan Wang; Ren-shan Ge; Jianfeng Ma (Chemico-Biological Interactions, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

Differential responses of soil microbial biomass and diversity to long-term phosphorus fertilization: A global meta-analysis - Jiahao Ge; Xiaoyi Han; Xinyue Lei; Qixuan Wang; Pengyue Wu; Nanhai Zhang; Yuying Guo; Pu Yang; Baili Feng; Jinfeng Gao (Agriculture, Ecosystems & Environment, 2026)

Liquid-liquid phase separation-driven enzyme catalysis for efficient biosynthesis of isoprenoid natural products - Han Wang; Bing-Bing Ma; Fei Cao; Ji-Jin Xie; Bei-Bei Wang; Shao-Yong Zhang; Ji-Dong Wang; Zha-Jun Zhan; Yu-Mei Ge; Xu-Ming Mao (Science China Life Sciences, 2026)

Parvimonas micra is a specifically enriched bacterium in advanced canine periodontal disease and its effects are ameliorated using ADSCs-exosomes - Miao Yu; Zheng Wang; Xiao Han; Yansong Ge; Zijian Geng; Jianfa Wang; Di Wang; Shuai Lian (Veterinary Microbiology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Substantial terrestrial export of dissolved organic carbon in China - Qian Yu; Han Li; Xiaodong Ge; Mingrui Ma; Wenxin Zhao; Jinya Yang; Jan Mulder; Lei Zhang; Yu Zhao; Lei Duan (Science Bulletin, 2026)

Research on high-efficiency region and condition of pectoral fin - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Ziqiang Ren; Han Ge; Haocai Huang (Ocean Engineering, 2026)

Genetic algorithm-optimized and explainable machine learning for bond strength prediction between steel-FRP composite bars and concrete - Zhiwen Zhang; Wenjie Ge; Shiwen Han; Ashraf Ashour; Dafu Cao; Jiangchuan Wu (Engineering Structures, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Lewis acid-mediated choline chloride-glycerol deep eutectic solvent pretreatment for Goji berry branches: Enhancing enzymatic saccharification and high-value utilization of lignin - Bingxue Sun; Huaitao Jiang; Guan-Ping Jin; Shi-Kui Han; Bolin Liu; Xiaoli Ge; Xiaoyou Xiu; Biaode Yang (Biomass and Bioenergy, 2026)

Dynamic Threshold Pressure Gradient Model of CO2 Injection into Coal Seams Based on Fractal Theory - Jing Han; Zhe Zhou; Zhaolong Ge; Jianming Shangguan; Jinming Cui (Rock Mechanics and Rock Engineering, 2026)

Phytolith-occluded carbon sequestration by Suaeda salsa in the Yellow River Delta estuarine channel shifts: opportunities for improved salt marsh management - Li Zhang; Bowen Rong; Changzi Ge; Xiangxing Gao; Cuilian Guo; Shaobin Han (Journal of Soils and Sediments, 2026)

ATP-dependent binding cassette transporter ClABCI6 promotes the expression of citrus yellow vein clearing virus via inhibiting salicylic acid pathway - Yaqin Song; Wen Ge; Cuiyun Lei; Yijie Li; Yang Han; Jiedan Xiao; Xinghua Qiao; Shixue Hu; Yan Zhou; Binghai Lou (Journal of Plant Research, 2026)

Potential Causes of Anti‐Phase Summer Precipitation Variability Between the Middle and Lower Reaches of the Yangtze River - Yuwei Zhou; Ge Liu; Xiaolu Yan; Sulan Nan; Ting Zhang; Yinghan Sang; Xuefeng Han; Yuhan Feng; Hancheng Zou (International Journal of Climatology, 2026)
Summer precipitation in the middle and lower reaches of the Yangtze River generally shows synchronous variability and is thus extensively studied as a unified climatic region. However, out‐of‐phase variations occur between the middle and lower reaches in some years. This study investigates the mechanisms of the positive middle Yangtze River precipitation (MYRP)–negative lower Yangtze River precipitation (LYRP) pattern from the perspectives of atmospheric circulation and land‐ocean thermal anomalies. The results suggest that a non‐canonical Silk Road Pattern (SRP) teleconnection in the upper troposphere, coupled with a mid‐to‐lower tropospheric anomalous anticyclone over Northeast Asia and a weakened western Pacific subtropical high (WPSH), contributes to this precipitation pattern. Further analysis reveals that colder‐than‐normal land thermal anomalies in the Greater Caucasus Mountains and the northeastern Tibetan Plateau, as well as warmer‐than‐normal sea surface temperature anomalies (SSTAs) in the Sea of Japan, may help maintain the SRP‐like Rossby wave train (SLWT), therefore influencing the positive MYRP–negative LYRP pattern. Linear baroclinic model sensitivity experiments further support the identified thermal anomalies can excite and maintain the SLWT. Given that the SLWT differs to some extent from the classical SRP in both wave source and downstream structure, this study also proposes a SLWT index based on 200‐hPa vorticity anomalies. This index effectively captures both the spatial structure of the SLWT and its link with out‐of‐phase precipitation anomalies between the middle and lower reaches of the Yangtze River and may serve as a potential indicator for the occurrence probability of the positive MYRP–negative LYRP pattern. These findings may improve our understanding of regional precipitation mechanisms in the Yangtze River basin, thereby providing a scientific basis for improved disaster prevention and mitigation strategies.

Ethyl ferulate attenuates allergic asthma via inhibiting macrophage M2 polarization through STAT6/IRF4 pathway - Longlong Ge; Weizhen Chen; Shuguang Han; Huan Yang; Mingchen Du; Shengpeng Li; Xinran Bai; Peilin Zhao; Dan Chen; Qingfeng Pang; Yaxian Wu (Inflammation Research, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

Determining Reference Intervals of Serum Biochemical Parameters in Juvenile Hybrid Snakehead Channa argus & C. maculata in Mesocosm - Jian Ge; Siyu Jiang; Lisha Yuan; Haichuan Chen; Qinghao Jin; Dong Han; Jian Wang (Fishes, 2026)
Hybrid snakehead (Channa argus × Channa maculata) is a major cultured freshwater fish in China, but standardized health monitoring using serum biochemistry is limited by the lack of species-specific reference intervals. This study established reference intervals for 20 serum biochemical parameters in hybrid snakehead reared under 27 °C for 90 days. The body weights of the sampled fish ranged from 50 g to 160 g and were exempted from diseases by health check. All parameters were measured using an automated analyzer with commercial reagent kits. Most parameters exhibited non-normal, right-skewed distributions, and only total protein (TP) was normally distributed. Smoothed bootstrap resampling and kernel density estimation were applied to extract the main peak distribution and reduce bias from outliers and long tails. Species-specific reference intervals were established based on the main peak data, providing more reliable physiological baselines than conventional percentiles. Correlation analysis revealed coordinated changes among liver function, nutrient metabolism, tissue damage, and digestive enzymes. These results provide a standardized tool for health assessment, subclinical disease diagnosis, and comparative analysis in juvenile hybrid snakehead maintained at an optimal temperature in indoor mesocosm systems.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Monitoring algal blooms in eutrophic inland lakes using OLCI: Overcoming cloud and sun-glint effects on low-quality imagery - Bingqian Han; Shaojing Wang; Long Fei; Kaishan Song; Ge Liu; Yue Ma; Shidi Shao; Yang Li; Yujin Zhou; Jipeng Zhang (Journal of Hazardous Materials, 2026)

A powdery biohybrid nano‑silver sensor based on phycoerythrin and carbon nanotubes for visual detection of Hg2+ in aquatic products - Chuanxu Liu; Xiangyu Lan; Changzhuo Zheng; Qinghao Ge; Xiaolong Han; Yang Pu; Wenjun Li (Algal Research, 2026)

A Galactose-Modified Light-Activatable Persulfurated Arene Fluorescent Probe for Targeted Imaging of Polarity and Viscosity in Liver Cancer Cells - Pan-Xin Ge; Yan Rong; Lu-Lu Sun; Yuqing Hu; Xianzhi Chai; Hai-Hao Han; Liangliang Zhu (Journal of Fluorescence, 2026)

Impact Mechanical Behavior and Energy Dissipation Analysis of Rock-Concrete Composites with different Interface Roughness - Wei-jing Yao; Han-bing Xu; Sheng-qi Yang; Shao-ge Rui; Jian-yong Pang (Applied Geophysics, 2026)

Source-sink dynamics of coastal blue carbon: a review of mechanisms and drivers - Meihong Ge; Jinfeng Du; Yunxiao Han; Lehong Chen; Xuefeng Xu; Yonglian Wang; Changbo Zhong; Dan Feng; Xiaoyan Wu (Frontiers in Marine Science, 2026)
Within the context of global climate change, coastal blue carbon ecosystems (e.g., mangroves, salt marshes, seagrass meadows, and macroalgae) have emerged as critical natural carbon sinks. Yet, persistent methodological inconsistencies and geographic biases hinder their reliable incorporation into blue carbon management and climate prediction. Here, we synthesize current understanding of source-sink characteristics, drivers, and formation mechanisms of coastal blue carbon ecosystems, focusing on carbon storage capacity, sequestration pathways, and spatial heterogeneity across ecosystem types. We emphasize biogeochemical processes, including sedimentation, tidal dynamics, and microbial mediation, and critically examine anthropogenic disturbances—coastal development, land-use change, pollution, and ecosystem degradation—on blue carbon dynamics. Finally, we identify critical knowledge gaps, particularly the quantification of lateral carbon fluxes and microbial carbon stabilization mechanisms, highlighting the need for integrated, multi-scale monitoring to better assess the climate mitigation potential of coastal blue carbon ecosystems.

l-Lysine effects on myosin carbonylation in metal-catalyzed oxidation: Implications for thermal gelation - Yuling Liu; Yuqi Wu; Ge Han; Jiaxin He; Yawen Wang; Jinfeng Pan; Shengjie Li (Food Research International, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Gap-filled spatiotemporal reconstruction of XCH4 data and analysis of methane emission patterns - Qian Xiao; Yong Wan; Ge Han; Yu Liu; Yuhang Liu; Xiaowen Li; Hongyu Zhou (Atmospheric Pollution Research, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

A Systematic Review of the Application of Chinese Satellite Observations for Water Quality Remote Sensing - Bingqian Han; Muhammad Bilal; Muhammad Usman; Meng Mu; Kaishan Song; Ge Liu; Zhidan Wen; Yingxin Shang; Chong Fang; Sijia Li; Shidi Shao; Yang Li; et al. (Chinese Geographical Science, 2026)

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Improved U-Net with enhanced spatiotemporal features for Chlorophyll-A concentration prediction in the Zhoushan fishery - Yanling Han; Yizhuo Cai; Ping Ma; Ge Song; Jing Wang; Yun Zhang; Shuhu Yang; Zhonghua Hong (Remote Sensing Applications: Society and Environment, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

Hydro-meteorological factors and human activities contribute comparably to weekly water quality dynamics in the Yangtze River Basin - Leifang Li; Taihua Wang; Ge Li; Han Cheng; Shulei Zhang; Dawen Yang (Journal of Hydrology, 2026)

Differential remediation of tetracycline vs. sulfamethoxazole-contaminated soils by ZVI/BC: Impacts on rice growth, soil properties, and key regulatory factors - Xu Su; Jie Han; Xuanming Wang; Siyu Wang; Yixuan Chen; Ziyi Ge; Jun Meng (Journal of Environmental Chemical Engineering, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Increased heterogeneity of sedimentary potential silicate-solubilizing bacterial communities caused by cascade damming reduces community complexity but promotes stability - Juan Chen; Qihao Nie; Chao Wang; Peifang Wang; Yuansheng Zhu; Ge Cui; Han Gao; Bo Zhang; Shunqing Zhang (Journal of Environmental Sciences, 2026)

Antimicrobial mechanism of green citrus peel extract against Gluconobacter cerinus causing decay in ‘Xuxiang’ kiwifruit - Juan Xie; Giri Raj Tripathi; Zhangxing Li; Hongyu Li; Xiaobo Liang; Peng Han; Ge Zhao; Miaomiao Yang (International Journal of Food Microbiology, 2026)

Scalable upcycling of medical plastic waste using metals-doped hierarchically porous biocarbon for tunable fuel-grade hydrocarbons or H2-enriched fuel gas - Guanyu Zhang; Qing Cheng; Ge Kong; Yuan Jiang; Xin Zhang; Tianqi Cao; Jingyou Bi; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Fuel, 2026)

Soil amendments improved physiological characteristics, grain yield, and water use efficiency of common buckwheat under multi-year continuous cropping - Qi Wang; Xiaoyi Han; Qixuan Wang; Minlong Du; Xinyue Lei; Jiahao Ge; Rong Zhong; Chenxi Wan; Xiaoli Gao; Pu Yang; Jinfeng Gao (European Journal of Agronomy, 2026)

Ecologically engineered seawall revetments for enhancing marine biodiversity: elevation and design options - Junbao Huang; Peng Yun; Yu Han; Qing Lyu; Huayu Chen; Zengfeng Li; Jiali Gu; Jian Zeng; Zhenming Ge (Coastal Engineering, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

In-situ Ag nanoparticle-embedded core-shell Cu-MOFs: enhanced photocatalytic activity for efficient degradation of petroleum oil spills in high-salinity seawater - Li Li; Guiguang Wu; Heng Luo; Ju Wang; Haijun Wu; Qianqian Hao; Yunxiao Han; Meihong Ge; Changbo Zhong; Yenan Wang (Frontiers in Marine Science, 2026)
Oil spill incidents occur widely around the globe, posing significant threats to the multifunctionality of coastal ecosystems, economic development, and human health. However, conventional oil contamination remediation approaches are plagued by inherent limitations, including low treatment efficiency, secondary pollution risks, and poor universality. To address this issue, a copper-based metal-organic framework (Cu-MOF) was synthesized via a solvothermal route in this study. Utilizing this Cu-MOF as a hard template, silver nanoparticles (Ag NPs) were immobilized within its cage-like porous channels through an in-situ reduction strategy, yielding a Ag@Cu-MOF composite photocatalytic material. The degradation performance of this composite toward oil pollutants derived from marine oil spills was systematically evaluated under UV-visible hybrid light irradiation. The experimental results demonstrated that when the loading content of Ag NPs was optimized to 5%, the composite achieved a degradation efficiency of 95.1% toward simulated oil spill pollutants (with crude oil employed as the model contaminant) at an initial concentration of 100 mg·L -1 within 2 hours. This degradation efficiency was significantly superior to that of pristine Cu-MOF (51.3%) and bare Ag NPs (25.9%). Mechanistic investigations revealed that the Localized Surface Plasmon Resonance (LSPR) effect of Ag NPs enables the extension of the material’s light response range to the visible spectral region. Concurrently, the Schottky junction formed at the interface between Cu-MOF and Ag facilitates the efficient separation of photogenerated electron-hole pairs, which remarkably enhances the photocatalytic activity of the composite. Furthermore, the Ag@Cu-MOF composite exhibited excellent structural and functional stability in a simulated seawater system with a salinity of 3.5% (mimicking real marine conditions). After four consecutive reuse cycles, the degradation efficiency remained above 88%, which not only validates the material’s reusability but also provides a novel material platform and technical paradigm for the efficient remediation of marine oil spills, holding great significance for advancing coastal ecological restoration practices.

Lower Plasma Serotonin is Associated with Higher Amyloid Burden, Hippocampal Atrophy, and Cognitive decline in Alzheimer’s Disease: A 24-Month Longitudinal Study - Yingbo Han; Li Liu; Li Chang; Xiaomin Ge; Qianqian Chen; Qian Li; Hehua Li; Wenchao Li (Journal of Molecular Neuroscience, 2026)

Simulating the impact of C/O ratio on chemical evolution of N-bearing species in the Hot molecular core - Wasim Iqbal; Xiaohu Li; Jixing Ge; Gleb Fedoseev; Xia Zhang; Yi-Han Wu; Fangfang Li; Zhenzhen Miao (Life Sciences in Space Research, 2026)

Mechanistic insights into magnetite-enhanced Indoleacetic acid production by a mixed culture - Yun-Xin Ge; Wei Gao; Zi-Han Fan; Yun Niu; Long-Tao Fang; Xi-Zhen Zou; Wei Zhang (Journal of Water Process Engineering, 2026)

Alleviating effects and mechanism of Lacticaseibacillus paracasei BHP06 on the allergic reactions induced by ovalbumin - Xiang-Ge Xin; Yue Meng; Jun Meng; Jun Xi; Chang-He Ding; Rui-Han Ge; Yu-Tong Bai; Ming-He Li (Food Bioscience, 2026)

Pulsed light improves the antioxidant activity and storage quality of postharvest hawthorn by regulating the γ-aminobutyric acid metabolic pathway - Mengpei Liu; Chenyang Wu; Jiale Wang; Lihua Zhang; Zhenzhen Ge; Weijuan Han; Xinyan Zhao (Food Bioscience, 2026)

Ion coordination competition enhanced adsorption strategy for improved thermopower in I−/I3− gel-based thermo-electrochemical cells - Qingxin Ge; Zhou Zhou; Jing Li; Xiangyang Qu; Qiaoqiao Fang; Zhiliang Han; Rongliang Wu; Huaping Wang; Shiyan Chen (Chemical Engineering Journal, 2026)

Development of Ce La bimetal oxyhydroxide nanocomposite with enhanced stability and selectivity for phosphate and fluoride co-removal from phosphogypsum leachate - Wenlan Yang; Yujie Du; Haoyuan Xu; Han Li; Zhiheng Li; Jingguo Fang; Chang Liu; Longjie Ge; Linyi Gao (Chemical Engineering Journal, 2026)

Unraveling plant immunity: from pathogen perception to resistance engineering - Fan Liu; Dongdong Ge; Guiwei Lian; Zhifu Han; Jijie Chai (Science China Life Sciences, 2026)

Root microorganisms enhance crop resistance to low-temperature stress by increasing antioxidant enzyme activity - Han Zhang; Junhui Li; Gang Chen; Youguo Zhan; Dekai Ning; Jiaqi Liu; Ruiwen Hu; Ge Tan; Qiyun Zhou; Juan Li; Zhengling Liu (Planta, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

Design and performance verification of crab seedling automatic counting equipment based on improved YOLOv11+DeepSORT - Changfeng Tian; Xuan Che; Lei Ge; Zhi Qu; Mengxia Han (Aquacultural Engineering, 2026)

Asymmetric Propagation of Hydraulic Fractures in Coal–Rock Composite Formations: Insights Based on Stress Sensitivity of Coal - Zhaolong Ge; Changzheng Lu; Qinglin Deng; Zhe Zhou; Shuo Dai; Jing Han; Jinming Cui (Rock Mechanics and Rock Engineering, 2026)

A Soft Bionic Pectoral Fin Actuated by a Series of Differential Gear Units - Chaowu Sheng; Liwen Nan; Qiaoling Gao; Jiawang Chen; Peng Zhou; Han Ge; Haocai Huang (Journal of Marine Science and Engineering, 2026)
The bionic pectoral fin serves as the primary propulsion component of ray-inspired robots. In our previous research, a motion equation was proposed for the real pectoral fin, which can be modeled as a series of NACA airfoil-shaped cross-sections distributed along the spanwise direction. Each cross-section undergoes two coupled rotational motions about its chord line and spanwise rotational axis. To achieve this type of motion, this article introduces a novel bionic pectoral fin mechanism driven by a series of differential gear units. The differential unit generates two coupled rotational motions corresponding to the cross-section of the pectoral fin in motion. A series of interconnected differential units provides a unique topology for the bionic mechanism and can generate a diverse range of motions. Through kinematic analysis, the motion equation was mapped onto the rotational angles of motors in the differential units. The proposed bionic mechanism was then fabricated and subjected to experimental test, demonstrating its effectiveness with a maximum thrust of 0.71 N. The distinctive structure of this bionic mechanism differentiates it from conventional designs and is expected to provide some inspiration for bionic pectoral fins and ray-inspired robots.

Sustainable alternative to biological nitrogen removal: Is ammonia recovery from municipal wastewater a fantasy? - Wenjie Hao; Yuanyuan Yu; Yi Gong; Ge’er Wang; Maoqin Ao; Minyuan Han; Haoquan Zhang; Qingxiang Guo; Jingmei Yao; Yi Yang; Zhongbo Zhou; Le Han (Water Research, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

A multi-strategy multi-population cooperative optimization algorithm for drinking water pollution source identification - Han Wang; Qinghua Wu; Yang Ge; Zhijun Ren; Xuesong Yan (Swarm and Evolutionary Computation, 2026)

Nitrogen fertilizer strategies modulate gaseous nitrogen losses and improve maize yield and nitrogen use efficiency under saline-alkali stress in coastal reclaimed farmland - Xiaoqing Wang; Jiayi Xie; Wenjing Li; Lijie Pu; Pengjun Chen; Jijun Han; Chenliang Du; Sihua Huang; Rui Zhang; Rui Zhong; Ye Yuan; Jiahao Zhai; et al. (Soil and Tillage Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Isolation and identification of Desmodesmus sp. HDMA-07: Nutrient removal and biodiesel production potential in flax fiber wastewater - Han Wang; Xinyi Wang; Boqi Wang; Yimeng Lin; Jingping Ge; Wenxiang Ping (Process Safety and Environmental Protection, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Exogenous melatonin alleviates heat stress-induced metabolic slowdown affecting broiler growth by improving lipid metabolism - Fei Song; Binglin Wang; Xin Kang; Aige Han; Huiyuan Rui; Xiangyang Xu; Yi Guo; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2026)

Inhibitors Enable Rapid Start-up and Stable Operation of Partial Nitrification: Effects, Mechanisms and Challenges - Yun Song; Xiaoyu Han; Shujun Zhang; Liang Zhang; Bo Wang; Da Kang; Zheng Ge; Yongzhen Peng (Journal of Environmental Sciences, 2026)

Attributing GHG emissions to individual facilities using multi-temporal hyperspectral images: Methodology and applications - Yichi Zhang; Ge Han; Yiyang Huang; Huayi Wang; Hongyuan Zhang; Zhipeng Pei; Yuanxue Pu; Haotian Luo; Jinchun Yi; Tianqi Shi; Siwei Li; Wei Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Ecological risk assessment of PAHs in surface sediments near Longkou Artificial Island (Laizhou Bay, China): Insights from content, source and toxicity equivalents - Yangmin Xu; Bin Han; Xiufang Zhang; Yinghui Liu; Yanan Ge; Li Zheng; Zheng Lu (Marine Pollution Bulletin, 2026)

Effects of ocean acidification on intestinal homeostasis and organismal performance in a marine bivalve: From microbial shifts to physiological suppression - Minggui Liu; Xiaoyu Guo; Lanfang Han; Yuanyuan Zhao; Chengjun Ge (Marine Pollution Bulletin, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Integrative mechanisms, dissolved oxygen control, and the optimal energy window for one–stage aerobic nitrogen and phosphorus removal via heterotrophic nitrification–aerobic denitrification (HN–AD) - Jiale Han; Xiaoyu Wang; Xinjiao Dong; Qi Fang; Zimiao Yan; Yaru Li; Shimei Ge (Journal of Water Process Engineering, 2026)

Uncovering the sensing power of shared bikes for urban feature monitoring - Wen Ji; Ke Han; Qi Hao; Qian Ge; Ying Long (Journal of Transport Geography, 2026)

Impact of temperature on the biogenic volatile organic compound (BVOC) emissions in China: A review - Yiming Yang; Fengbin Sun; Yusheng Chen; Shiyue Yang; Yuan Dai; Yiming Qin; Ning Zhang; Zhifeng Shu; Han Yan; Xinlei Ge; Junfeng Wang (Journal of Environmental Sciences, 2026)

Wide-targeted metabolomics elucidates metabolic compartmentalization and pathway enrichment in Leontopodium leontopodioides (Wild.) Beauv. Organs - Rule Yi; Gentu Ge; Junfeng Hao; Feng Han; Zhuna Bao; Yuqi Zou; Mingga Qi (Food Bioscience, 2026)

Seasonal transmission characteristics, interconnections and risk assessment of bioaerosol-mediated ARGs and bacteria in the underground wastewater treatment plant - Jingyun Ge; Hongyu Tian; Jianwei Liu; Jianbin Sun; Yunping Han (Environmental Research, 2026)

Innovative NFC-based flexible sensing system for wireless and battery-free detection of H2S: A game-changer in real-time fresh food freshness evaluation - Ning Shi; Yan Tong; Boyang Xu; Xiaohu Ge; Yueqiang Cao; Yu Han; Yunda Chen; Anxin Luo; Xiaochan Wang; Gang Liu; Xiande Zhao; Guo Zhao (Chemical Engineering Journal, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Targeting P2X7R Protects the Retina Against High-Altitude Hypoxia via NLRP3–Mediated Pyroptosis Suppression - Keke Ge; Yange Gu; Huan Xi; Siyuan Liu; Yatao Wang; Lu Yang; Cong Han; Xingxing Zheng; Hao Wang; Songjian Huang; Wenfang Zhang (Molecular Neurobiology, 2026)

Time-Resolved Oxidative Stress and Apoptosis in Murine Retina under Acute Hypobaric Hypoxia with Parallel Activation of the LIF–JAK–STAT3 Axis - Hao Wang; Qiang Ye; Songjian Huang; Keke Ge; Cong Han; Huan Xi; Junyi Qiao; Jingrong Feng; Peirun Wu; Yuhan Bao; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Influence of Grouting Pipe Lifting Rate on Vacuum Preloading Performance for Dredged Sludge - Zhou Changchen; Jin Fangyi; Xu Li; Li Dawei; Ni Junfeng; Yan Shuaixin; Xu Mintao; Han Song; Ge Bin; Wu Yehu; Zhang Ye (Geotechnical and Geological Engineering, 2026)

Effects of organic fertilizer substitution for chemical fertilizer on tea yield and quality: A meta-analysis focusing on alkali-hydrolyzable nitrogen dynamics - Shaobo Zhang; Hongbin Zhang; Lan Zhang; Zhengzhen Li; Yihu Mao; Liping Zhang; Shibei Ge; Qiang Hu; Chao Chen; Wenyan Han; Peng Yan; Xin Li (Soil and Tillage Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

First global XCO2 observations from spaceborne lidar: methodology and initial result - Ge Han; Hongyuan Zhang; Yiyang Huang; Weibiao Chen; Huiqin Mao; Xingying Zhang; Xin Ma; Siwei Li; Haowei Zhang; Jiqiao Liu; Feiyue Mao; Wei Gong (Remote Sensing of Environment, 2025)

Ship trajectory prediction under multi-ship coupling effect based on a generative adversarial network - Xiao Li; Zhaokun Wei; Qiang Zhang; Lei Xing; Zhifeng Han; Ge Gao (Ocean Engineering, 2025)

Rainfall process-related dissolved organic carbon wet deposition at the southern foot of Qinling Mountain: Implications for atmospheric carbon budget at the boundary area between north and south China - Jie Zeng; Guilin Han; Qixin Wu; Lihong Fu; Qing Ma; Jie Zhang; Xinyi He; Xin Ge (Journal of Hydrology, 2025)

Seasonal and diurnal variations of pCO2 from reservoirs and lakes in Northeast China - Shiwei Liu; Zhidan Wen; Ge Liu; Yingxin Shang; Junbin Hou; Hui Tao; Chong Fang; Sijia Li; Xiangfei Yu; Jiarui Han; Jiping Liu; Kaishan Song (Journal of Hydrology, 2025)

Multiomic insights into the regulatory mechanism of anammox consortia: Interspecies cooperation, degradation and self-adaptation to plasticizer stress - Ge-Ge Wu; Jing-Ao Jin; Na-Na Han; Wen-Li Guo; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Application of machine learning in soil fumigation remediation prediction and design - Qingli Han; Liqing Ge; Yuanchuan Ren; Youshun Yu (Journal of Environmental Chemical Engineering, 2025)

Green reagent-driven resource recovery: Separation of hematite and iron-bearing silicate minerals from complex low-grade iron ore - Wencheng Ge; Zixuan Guo; Jie Liu; Yimin Zhu; Shuai Yuan; Peng Gao; Xiaolong Zhang; Yuexin Han (Journal of Environmental Chemical Engineering, 2025)

Proteomic and flavor dynamics in irradiated scallop adductor muscle during refrigerated storage via 4D-DIA proteomics - Zhupeng Zhang; Peng Ge; Chaoqi Han; Jie Zhang; Richeng Yu; Wenxiu Wang; Ran Suo; Jianfeng Sun (Food Chemistry, 2025)

Effect of electron beam irradiation on physicochemical and protein properties of scallop adductor muscles during cold storage - Zhupeng Zhang; Peng Ge; Chaoqi Han; Fan Zhang; Wenxiu Wang; Ran Suo; Qianyun Ma; Zhenzhen Wang; Jianfeng Sun (Food Chemistry, 2025)

Latitudinal transitions of eddy-affected zooplankton abundance in the mid-latitude North Atlantic - Guiyan Han; Graham D. Quartly; Hui Wang; Jie Yang; Ge Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Gold nanoparticles recovered from e-waste by one-dimensional covalent organic framework for highly efficient reduction of nitrophenols - Wenping Yao; Bangdi Ge; Yuze Chen; Wenyu Jiao; Hao Han; Xiaowei Song; Zhiqiang Liang (Chemical Engineering Journal, 2025)

Roll-to-roll fabrication of paper-tape electrochemical sensing devices for point-of-care testing - Xinghua Du; Ruping Liu; Yicheng Chen; Hongbo Shan; Lu Han; Yongsheng Cai; Lihui Ke; Jiafeng Chen; Li Wang; Bo Wei; Changjiang Ge; Minghua Du; et al. (Chemical Engineering Journal, 2025)

Chitosan-derived nanoemulsion enriched with Streptomyces metabolites for target control of tobacco leaf spot, enhanced foliar retention and plant nutrition - Xue Han; Chunli Xu; Rui Yang; Dan Chen; Yaning Li; Beibei Ge (Chemical Engineering Journal, 2025)

Effects on soil structures by root growth in the Loess Plateau, China - Rongqi Li; Hanruo Wang; Yilin Yan; Chao Han; Yulong Zhao; Yuanhao Liu; Shangyu Shi; Wenyan Ge; Fei Wang (CATENA, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

In-situ visual delignification and cell-scale kinetics modeling using confocal Raman microscopy - Yuanping Huang; Zengling Yang; Chenjun Ge; Zhuolin Shi; Xinlei Wang; Lujia Han (Bioresource Technology, 2025)

Waste wood in agroforestry systems improves phallus dongsun yield by regulating soil bacterial interactions and improving soil properties - Wei Ge; Yang Gui; Guosheng Zhu; Wanbing Huang; Biao Li; Hongyu Liu; Yingying Lu; Qingcheng Liu; Chunbo Dong; Yanfeng Han (Applied Soil Ecology, 2025)

Paper production and usage in the late fourteenth century in northern China: insight from paper fragments unearthed at the Dove Cave site - Ruoxi Guang; Xiaoqiang Wang; Mengfan Ge; Xiuming Lv; Yimin Yang; Mingwu Zhang; Bin Han (Archaeological and Anthropological Sciences, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

From photosynthesis to grain formation: A comprehensive evaluation of nitrogen-phosphorus co-optimization strategies in mung bean (Vigna radiata L.) cultivation - Jiahao Ge; Xiaoyi Han; Qi Wang; Rong Zhong; Shaofei Li; Qixuan Wang; Enlei Li; Qingming Wang; Feng Gao; Baili Feng; Jinfeng Gao (Field Crops Research, 2025)

Chlorine-anion doping enhances the metal-oxygen covalency of Bi0.5Sr0.5FeO3-δ air electrode: achieving superior catalytic activity for reversible solid oxide cells - Hui Ye; Zhipeng Miao; Yanfeng Fu; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng; Sheng Cui (Chemical Engineering Journal, 2025)

Fs–LA–ICP–MS U–Pb dating of fluorite and its prospect for geological application - Yan-Wen Tang; Na Liu; Jun-Jie Han; Yan Liu; Wan-Ting Ge; Jian-Feng Gao; Ting-Guang Lan (Chemical Geology, 2025)

Mitomycin C-induced prophage activation for exploring the Lysogeny-lysis functional dynamics in situ - Ruoyi Xu; Tida Ge; Yuchuan Fan; Lu Yang; Ying Zhang; Siqin Han; Mark Radosevich; Xiaolong Liang (Applied Soil Ecology, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Significant enhancement of inhibitory strength of bisphenol A analogs against human and rat 5α-reductase 1 upon halogenation of the benzene ring: Potentially disrupting neurosteroid biosynthesis - Shihan Wang; Shaowei Wang; Han Lu; Binbin Lu; Huitao Li; Yingfen Ying; Ren-shan Ge; Yunbing Tang (Toxicology and Applied Pharmacology, 2025)

Enhancing spatiotemporal coverage of satellite-derived high-resolution NO2 data with a super-resolution model - Maolin Zhang; Siwei Li; Jia Xing; Ge Song; Shuangliang Li; Jiaxin Dong; Shuxin Zheng; Ge Han; Jie Yang (Remote Sensing of Environment, 2025)

Degradation-catalysis of polypropylene into liquid fuel-range iso-olefins using Zn and Ni-incorporated microporous carbon - Qing Cheng; Guanyu Zhang; Wei Li; Yuan Jiang; Ge Kong; Xin Zhang; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2025)

Morphology and community structure characteristics of aerobic granular sludge: A review - Peixin Liu; Yue Yang; Ma Ge; Qinghui Luo; Bin Cui; Han Cui; Tingting Cao; Dandan Zhou (Journal of Environmental Chemical Engineering, 2025)

In situ growth of NiCo2O4 nanosheets on N,S co-doped rice husk biochar for ultrasensitive and selective Pb2 + and Cd2+ electrochemical sensing - Mingmei Ge; Xinying Han; Rui Wang; Chenxi Wu; Shiyu Wang; Bao Chang; Zhuang Miao; Yang Zhao; Huan Wang (Journal of Environmental Chemical Engineering, 2025)

Warming coupled with uranium exposure can alter the marine microbial community and induce toxin accumulation in shellfish - Ran-li Wang; Qian Fu; Ge Yao; Jin-long Lai; Shao-heng Bao; Xue-gang Luo; Hui Jiang; Yu Zhang; Peng-gang Han (Journal of Environmental Radioactivity, 2025)

Fracture evolution and anchoring mechanisms in discontinuous rock masses with irregular joints: Discrete element study using a novel damage constitutive model - Yin-Ge Zhu; Yue Wu; Cheng-Hao Han; Wei-Guo Qiao; Feng Jiang; Ji-Xian Dong; Shuai Zhang; Yan-Zhi Li (Computers and Geotechnics, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

First Isolation of a Multi-azole-Resistant Aspergillus fumigatus cyp51A TR46/Y46F/F70L Mutant in a Patient with Fungal Keratitis - Xiang Han; Heng Zhang; Yuqi Mao; Wenhao Ling; Lu Ge; Menghua Tang; Yi Sun; Zhiqin Wu (Mycopathologia, 2025)

SPPF-CGA: Marine Garbage Detection and Image Enhancement in Turbid and High-Dynamic Underwater Environments - Jinhuan Wang; Qingbang Han; Kao Ge; Liujia Sun (Journal of Ocean University of China, 2025)

Plasma-Derived Exosomal tRF-Phe-GAA-001 and tRF-Gly-GCC-037 as Novel Diagnostic Biomarkers for Cervical Cancer - Zheng Li; Hongyan Wang; Ruijun Yang; Xiangchun Jin; Qing Han; Zhaoyuan She; Peng Ge (Indian Journal of Clinical Biochemistry, 2025)

Breaking the legume intensification paradox: Precision nitrogen-phosphorus fertilization for optimizing biological nitrogen fixation, yield, and soil physicochemical properties in mung bean - Jiahao Ge; Qi Wang; Enlei Li; Siyuan Zhang; Xaioyi Han; Shaofei Li; Qixuan Wang; Qingming Wang; Pengyue Wu; Feng Gao; Baili Feng; Jinfeng Gao (Applied Soil Ecology, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Machine Learning-Assisted Diagnosis of Abrupt Air Pollution Emissions: Insights From Firework Emissions in China - Lu Yang; Di Liu; Han Yang; Jie Fang; Qingxiao Meng; Yunjiang Zhang; Xinlei Ge (Aerosol Science and Engineering, 2025)

Sex-Associated Indels and Candidate Gene Identification in Fujian Oyster (Magallana angulata) - Yi Han; Yue Ning; Ling Li; Qijuan Wan; Shuqiong Li; Ying Yao; Chaonan Tang; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Fishes, 2025)
Sex determination is a fundamental biological process governing animal reproduction. Although substantial progress has been made in elucidating its genetic basis, the genetic architecture underlying complex sex determination systems remains poorly understood. In this study, we identify sex-associated insertion–deletion (indel) variants, screen candidate genes, and compare sex-associated variation across populations with different genetic backgrounds in the Fujian oyster (Magallana angulata). Based on whole-genome resequencing data of a culture strain (designated FL), a total of 299,774 high-quality indels were identified. By integrating genome-wide association analysis (GWAS), fixation index (FST) analysis, and sex-biased genotype frequency comparisons, 77 overlapping sex-associated indels were identified, predominantly clustered within a 1.8 Mb (8.3–10.1 Mb) region on chromosome 9. Principal component analysis (PCA) based on the sex-associated markers and their subsets consistently separated male and female individuals in the FL strain. For two representative sex-associated indels, PCR-based genotyping methods were developed and validated. Functional annotation identified putative candidate genes for sex determination, including PKD1L1, 5-HTRL, SCP, and CCKRa. Comparative analysis of variants within PKD1L1 across wild, farmed, and selectively bred populations revealed a progressive enrichment of male-linked alleles in domesticated and selectively bred groups, particularly in male individuals. This study provides direct evidence that sex in the Fujian oyster is genetically determined and reveals that domestication and artificial selection may drive the emergence of major sex-determining loci, offering important insights into the genetic basis of sex determination in the Fujian oyster, and establishing a theoretical and practical foundation for molecular marker-assisted breeding of monosex lines for this species.

Combined effects of tree canopy and root systems on soil hydraulic properties: A field monitoring of a Populus alba - Xu-Guang Gao; Ji-Peng Wang; Xian-Wei Li; Shangqi Ge; Huan-Xiang Qiu; Mo-Han Bai (Rhizosphere, 2025)

Biodegradation of poly(butylene adipate-co-terephthalate) film by heat-tolerant bacterium Bacillus sp. PBAT4 - Yulong SUN; Lei GE; Ling WANG; Han WU; Michael Gatheru WAIGI; Juan LIU (Pedosphere, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Promoting the butterfly transformation of residual sludge: Specific adsorption of heavy metals and in-situ cultivation of granular sludge - Tingting Cao; Qinghui Luo; Peixin Liu; Ma Ge; Liang Liu; Xiyang Fei; Yuanhang Zhao; Bin Cui; Han Cui; Dandan Zhou (Journal of Hazardous Materials, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

TAM-TR: Text-guided attention multi-modal transformer for object detection in UAV images - Jianhao Xu; Xiangtao Fan; Hongdeng Jian; Chen Xu; Weijia Bei; Qifeng Ge; Teng Zhao; Ruijie Han (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Simultaneous determination of pesticide residues and rapid discrimination of corn production origin using ambient ionization mass spectrometry combined with machine learning - Hang Su; Lifeng Han; Miaoxiu Ge; Xiangyu Wang; Hongping Zeng; Dan Zhao; Wei Xiong; Luhong Wen (Food Chemistry, 2025)

Preparation, characterization and biological activity of Pteridium aquilinum polysaccharide-Cu(II)/Zn(II) complexes in vitro - Zhe-Han Zhao; Hai-Jiang Zhang; Xiao-Ji Cao; Bin Wu; Yi-Chao Ge; Kui-Wu Wang (Food Bioscience, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Efficient perfluorooctanoic acid degradation using by a vacuum ultraviolet-activated dithionite reduction system: Reactive species, process optimization, degradation pathways, and toxicity changes - Jinmin Su; Tao Lin; Yuchen Wang; Han Chen; Xinran Ge (Chemical Engineering Journal, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Fe and Mn biogeochemical cycling associated with basin-scale redox dynamics traced by DOM degradation in different alluvial aquifers - Jiaqi Jiang; Chunli Su; Han Geng; Yanxin Wang; Weili Ge; Hongjie Pan; Xianjun Xie; Guojie Feng (Water Research, 2025)

Effects of reversing the light-dark cycle on growth performance and intestinal health in heat-stressed broilers - Huiyuan Rui; Xiangyang Xu; Fei Song; Aige Han; Meiwei Lv; Xin Kang; Ming Ge; Xiaowen Jiang; Wenhui Yu (Journal of Thermal Biology, 2025)

Polarization of dryland vegetation response to spring flood - Shouguo Zhang; Han Wang; Xiwen Zhang; Guanglei Li; Ling Zhang; Chang Ge; Jiabin Wang; Jiansheng Wu; Jian Peng (Journal of Environmental Management, 2025)

How renewable energy policies cut greenhouse gas emissions: Insights from advanced data analysis techniques - Xinyue Gao; Yujie Ge; Jiansheng Qu; Jinyu Han; Tek Narayan Maraseni; Chunsen Liu; Kemin Huang; Li Xu; Dai Wang; Hengji Li (Journal of Environmental Management, 2025)

Weathering and recycling controls on rare earth element behavior: A comparative study on granitic, basaltic and aeolian red soil crusts - Long Han; Bin Lü; Chaoqiang Li; Jiao Yang; Wenjing Ge; Jianlei Gao; Xingxing Wang; Yan Zheng (Geochimica et Cosmochimica Acta, 2025)

Use of stable isotopic signatures and fatty acid profiles to authenticate Chinese mitten crab (Eriocheir sinensis) reared in ponds and rice fields - Cui Han; Yujing Xiao; Zhongqi Dai; Lei Feng; Yan Shi; Xiaojie Liu; Jiachun Ge; Jiaxin Yang (Food Control, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

The synergistic impact of cadmium and the wheat rhizosphere on the soil bacterial community in alkaline cropland in Northern China - Wenjing Ge; Fukun Gao; Jianlei Gao; Junxiang Ding; Long Han; Jing Wang; Tengyun Zhang; Hongli Li; Yixin Yan (Journal of Soils and Sediments, 2025)

Synergistic genetic module engineering for optimized eicosapentaenoic acid production in Nannochloropsis oceanica - Jie Zheng; Ye Liu; Feng Ge; Cheng-Cai Zhang; Danxiang Han; Haiyan Ma (Algal Research, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

Enhancing water security in lake basins through geographic intelligence technology - Yong Ge; Li Zhang; Yi Han; Die Zhang; Wenjing Yang; Lian Feng; Jinwei Dong; Shuping Wang; Simin Peng; Chaoyang Fang (Science Bulletin, 2025)

Novel insights into the DOM-driven processes affecting nitrogen cycling in shallow aquifers of the West Liao River Plain: Evidence from FT-ICR MS and isotope analyses - Jiaqi Jiang; Chunli Su; Han Geng; Yanxin Wang; Weili Ge; Hongjie Pan; Xianjun Xie; Guojie Feng (Journal of Hydrology, 2025)

Quorum sensing-mediated microecological homeostasis in anammox consortia - Jia-Hui Yang; Dong-Qi Huang; Ge-Ge Wu; Na-Na Han; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Differential size-dependent response patterns and antibiotic resistance development mechanism in anammox consortia - Na-Na Han; Jun-Hui Yang; Ge-Ge Wu; Jia-Hui Yang; Jing-Ao Jin; Nian-Si Fan; Ren-Cun Jin (Journal of Hazardous Materials, 2025)

Synthesis of high yield mesoporous silica for efficient CO2 adsorption using coal gasification fine slag - Zekai Miao; Hao Ge; Xinran Han; Rui Wu; Hai Zhu; Congchao Zhang; Shengping Wang (Fuel, 2025)

Route planning of mobile sensing fleets for repeatable environmental monitoring tasks - Wen Ji; Ke Han; Qian Ge (Computers, Environment and Urban Systems, 2025)

Correction: Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Xiaoyan Zhou; Yue Ning; Jingyi Xie; Yi Han; Chaonan Tang; Caiyuan Su; Qijuan Wan; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Frontiers in Marine Science, 2025)

Identification of sex-linked markers and genes in Portuguese oyster (Magallana angulata) - Xiaoyan Zhou; Yue Ning; Jingyi Xie; Yi Han; Chaonan Tang; Caiyuan Su; Qijuan Wan; Qisheng Wu; Xiang Guo; Jianfei Qi; Yizhou Ke; Hui Ge; et al. (Frontiers in Marine Science, 2025)
The Portuguese oyster ( Magallana angulata ) is a valuable aquaculture species with sexual dimorphism in growth and nutritional traits, making it a promising candidate for sex-controlled breeding. However, the genetic mechanisms underlying its sex determination remain poorly understood. This study represents the first population-level investigation to identify sex-linked genetic markers and candidate genes in M. angulata using genome-wide association studies (GWAS) and transcriptomic analysis. A total of 1,613 sex-associated SNPs were identified, primarily located on Chr. 9 (7.99 Mb–10.51Mb). SNP annotation revealed 57 genes around these sex-associated SNPs. Transcriptomic analysis identified 8,635 differentially expressed genes (DEGs) between male and female gonads, of which 12 overlapped with GWAS-identified genes. Among these, four genes ( 5-HTR , ADPKD1-a , SCP , and SLC28A3 ) exhibited strong sex-specific genetic differentiation, with 5-HTR showing the most pronounced association. Further population genetic analysis revealed higher genetic diversity and heterozygosity of 5-HTR in males. Six sex-associated haplotypes based on SNPs within 5-HTR were constructed and validated in an independent population, although with reduced significance, suggesting both continuity and variation in sex determination mechanisms across populations. These findings provide a critical foundation for understanding the genetic basis of sex determination and advancing sex-controlled breeding strategies in M. angulata.

Towards clean energy technologies: Assessing the supply potential of critical rare earth elements in China - Han Ding; Jianping Ge (The Extractive Industries and Society, 2025)

Study of enhanced nitrogen removal performance and mechanism of iron-modified activated carbon in low-temperature environments - Guangtao Li; Jinlong Han; Yunchang Wang; Shihong Wu; Liyan Ge; Xueqian An; Xiaoyang Liu; Wenfang Gao; Li Sun; Zhijun Ren; Kengo Kubota (Journal of Environmental Chemical Engineering, 2025)

Interspecies interactions promote dual-species biofilm formation by Lactiplantibacillus plantarum and Limosilactobacillus fermentum: Phenotypic and metabolomic insights - Bingxin Zhang; Yuxin Sun; Wenyu Han; Wenwen Ge; Zhenbo Xu; Shuo Wang; Zhenquan Yang; Lei Yuan (Food Research International, 2025)

Overall quality changes of fresh-cut cowpeas (Vigna unguiculata L. Walp.) during storage: Correlation of packaging materials and quality - Wen Zhang; Mengtong Han; Yubin Wang; Zhiwen Ge; Wanfu Hou; Liqun Zhao; Xiaoyan Zhao; Dan Wang (Food Chemistry, 2025)

Multifunctional and structural magnetic nanobranches for high-efficiency biological detection - Wenxu Hu; Yongliang Dong; Tianxin Ge; Si-Yang Liu; Jianhe Guo; Liqiu Wang; Changqing Yi; Xing Han; Zong Dai (Chemical Engineering Journal, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Foxp3 inhibits PCV2 replication by reducing the ATPase activity of Rep - Ruijiao Jiang; Qiuyan Huang; Ruiting Shen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2025)

Island-shaped micro-cracks evolution in ultrathin film enables ultra-sensitive for strain sensors under high temperatures - Ge Wang; Yifan Zhao; Ziang Wang; Jian Wang; Song Wang; Yaxin Zhang; Kun Zheng; Feng Han; Chenying Wang; Zhuangde Jiang (Chemical Engineering Journal, 2025)

Multiscale modelling and simulation of coal separation process in a pilot-scale gas–solid fluidized bed - Ying Jia; Yong Zhang; Wei Han; Xianqiang Xiong; Enhui Zhou; Ji Xu; Chenlong Duan; Yuqing Feng; Yuemin Zhao; Wei Ge (Chemical Engineering Journal, 2025)

Biomedical data and AI - Hao Xu; Shibo Zhou; Zefeng Zhu; Vincenzo Vitelli; Liangyi Chen; Ziwei Dai; Ning Yang; Luhua Lai; Shengyong Yang; Sergey Ovchinnikov; Zhuoran Qiao; Sirui Liu; et al. (Science China Life Sciences, 2025)

Comparative Analysis of Human Brain RNA-seq Reveals the Combined Effects of Ferroptosis and Autophagy on Alzheimer’s Disease in Multiple Brain Regions - Ke Ye; Xue Zhao; Lulu Liu; Fangliang Ge; Feifei Zheng; Zijie Liu; Mengjie Tian; Xinyu Han; Xu Gao; Qing Xia; Dayong Wang (Molecular Neurobiology, 2025)

Tim-3 Deficiency Ameliorates Motor Deficits and Neuroinflammation in MPP+/MPTP-Induced Parkinson’s Disease Models via the NF-κB/NLRP3 Pathway - Xi Yin; Ge Li; Fei Ji; Miao Wang; Yang Gao; Fengzhu Li; Zhenfu Wang; Gencheng Han; Zhongbao Gao (Molecular Neurobiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

Myeloid-derived suppressor cells alleviate adverse ventricular remodeling after acute myocardial infarction - Yan-Ge Wang; Ding-Hang Wang; Wen-Hui Wei; Xin Xiong; Jing-Jing Wu; Zhan-Ying Han; Long-Xian Cheng (Molecular and Cellular Biochemistry, 2025)

PLAGL2-STAU1-NCOA4 axis enhances gastric cancer peritoneal metastasis by resisting ferroptosis via ferritinophagy - Shansong Huang; Peicheng Ji; Peng Xu; Kanghui Liu; Han Ge; Zhengyuan Yan; Quan Cheng; Jialun Lv; Diancai Zhang (Apoptosis, 2025)

Redox condition changes in the Ross Sea, Antarctica, since the last glacial maximum - Yizhuo Wang; Yi Zhang; Xibin Han; Li Lin; Yukai Hong; Rui Han; Yun Liu; Pengyun Ma; Qian Ge; Xiaohu Li (Acta Oceanologica Sinica, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Solvent-free upcycling of agricultural plastic waste using in situ self-assembly metal nanoparticles co-doped microporous carbocatalyst for advanced transportation fuels - Ge Kong; Xiangru Yuan; Xiaojing Zhao; Jin Wang; Weizheng Zhong; Rongbin Qiu; Kai Song; Qing Cheng; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2025)

Satellite remote sensing of turbidity in Lake Xingkai using eight years of OLCI observations - Jian Li; Yang Li; Kaishan Song; Ge Liu; Shidi Shao; Bingqian Han; Yujin Zhou; Heng Lyu (Journal of Environmental Management, 2025)

A method to quantify the ecological benefits of river treatment projects with monetary values - Yadong Zhang; Zongkun Li; Wei Ge; Jiabao Wang; Han Wang (Journal of Environmental Management, 2025)

The dynamics impact of phlorizin on gut microbiota and metabolites in an in vitro fermentation model - Dingzuo Ge; Luyao Zheng; Li Liu; Xin Chen; Jiawei Zhou; Han Ge; Liqiang Guo; Hua Hua; Ruirui Wang; Lei Zhang (Food Research International, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Improving the catalytic activity and sintering resistance of Ni-BaCe0.7Zr0.1Y0.1Yb0.1O3−δ cermet anode for ammonia-fueled protonic ceramic fuel cells via Cobalt addition - Bangze Wu; Xiaole Yu; Zenan Zhao; Bingyu He; Zhanheng Jin; Zhexiang Yu; Qing Ni; Shoucheng He; Han Chen; Yifeng Zheng; Sheng Cui; Lin Ge (Chemical Engineering Journal, 2025)

A high-precision saltwater ice thickness and salinity detection method based on capacitive coupled planar microwave resonator - Han Shi; Mengjie Song; Junfeng Ge; Long Zhang; Xuan Zhang (Cold Regions Science and Technology, 2025)

Procyanidins-Mediated Biological Denitrification Inhibition Reduces Fertilizer-Induced N2O Emissions in Acidic Tea Plantation Soils - Xing Han; Haiyang Yu; Miaoling Meng; Chaorong Ge; Ningguo Zheng; Huaiying Yao (Journal of Soil Science and Plant Nutrition, 2025)

Pseudorabies virus inhibits the unfolded protein response for viral replication during the late stages of infection - Peng Gao; Jianle Ren; Qiongqiong Zhou; Peng Chen; Ailin Zhang; Yongning Zhang; Lei Zhou; Xinna Ge; Xin Guo; Jun Han; Hanchun Yang (Veterinary Microbiology, 2025)

C-C motif chemokine ligand 5 contributes to radon exposure-induced lung injury by recruiting dendritic cells to activate effector T helper cells - Liping Ma; Yilong Wang; Junwang Guo; Xuewen Zhang; Shuang Xing; Benbo Liu; Guo Chen; Xu Wang; Jiyao Hu; Ge Li; Gencheng Han; Maoxiang Zhu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Evaluating hydraulic permeability of hydrate-bearing porous media based on broadband electrical parameters: A numerical study - Lanchang Xing; Shuo Wang; Xiaofei Wu; Liyun Lao; Seyed Milad Salehi; Wei Wei; Weifeng Han; Donghui Xing; Xinmin Ge (Gas Science and Engineering, 2025)

Associations of preconception air pollution exposure with growth trajectory in young children: A prospective cohort study - Jiawen Liao; Weili Yan; Yi Zhang; Kiros Berhane; Wu Chen; Zhenchun Yang; Chenyu Qiu; Yihui Ge; Zhipeng Bai; Bin Han; Jia Xu; Yong-hui Jiang; et al. (Environmental Research, 2025)

Corrigendum to ‘Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure’ [Environ. Pollut. 347 (2024) 123742] - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2025)

Carbon emissions assessment of ultra-high performance concrete in construction industry: Calculation method and case study - Sheng Li; Ge Han; Boshi Du; Zhisheng Jiang; Linqi Sun (Energy and Buildings, 2025)

Engineered silicon-titania heterojunction elicits catalytic cancer cell death - Deliang Xu; Tingting Xu; Min Ge; Shibo Cao; Zhaoda Yu; Zhixin Chen; Ya-Xuan Zhu; Zhuang Liu; Ming Zong; Han Lin; Jianlin Shi (Chemical Engineering Journal, 2025)

Assessing carbon storage in Xinjiang’s arid grassland Ecosystems: Insights from Process-Based modeling - Haiyan Han; Jianli Ding; Jinjie Wang; Annan Zeng; Xiangyu Ge; Xiaowen Zhu (CATENA, 2025)

Electrostatic repellent dispersion method for green and cost-effective aqueous radiative cooling paint - Jipeng Fei; Di Han; Kai Zhou; See Wee Koh; Junyu Ge; Jun Yan Tan; Bing Feng Ng; Zhong Chen; Lili Cai; Hong Li (Building and Environment, 2025)

In-situ monitoring of clamp-repair-induced displacements in the submarine pipeline using a MEMS accelerometer array: A sea trial - Xueyu Ren; Jiawang Chen; Peng Zhou; Zhangyong Jin; Han Ge; Yulin Si; Yiyuan Zhang; Xiaoqing Peng; Xuehua Chen; Yunchao Peng (Ocean Engineering, 2025)

Far-field response to the closure of the Meso-Tethys Ocean: New geochronological evidence from the Chem Co graben in the westernmost part of Central Tibet - Yong Zheng; Jiawei Pan; Haibing Li; Zuolin Tian; Dongliang Liu; Mingkun Bai; Shuai Han; Chenglong Ge; Haijian Lu; Ning Zhong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Isolation and characterization of high ammonium tolerant Fasciculochloris sp. HDMA-06 and its potential for nutrient removal and biodiesel production in simulated swine wastewater - Han Wang; Xinyi Wang; Jixin Liu; Yimeng Lin; Jingping Ge; Wenxiang Ping (Journal of Water Process Engineering, 2025)

Drivers of ecological drought recovery: Insights from meteorological and soil drought impact - Chenhao Ge; Peng Sun; Rui Yao; Yayi Zhang; Han Shen; Huilin Yang (Journal of Hydrology, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

Optimized acid leaching synthesis and steam regeneration of the steel slag-derived calcium-based sorbent for enhanced CO2 capture - Nai Rong; Xiuliang Shi; Shanshan Wang; Long Han; Kaiwei Liu; Lichao Ge; Yuhan Wang; Geng Wang (Journal of Cleaner Production, 2025)

Have human activities been accurately evaluated in sediment yield changes in the middle reaches of the Yellow River? - Yuanhao Liu; Fei Wang; Shuyu Zhang; Hanruo Wang; Chao han; Rongqi Li; Jianqiao Han; Wenyan Ge; Hao Chen; Shangyu Shi (Journal of Environmental Management, 2025)

The relationship between indoor airborne culturable bacteria with passenger flow in 132 traffic stations during 2019–2020, China - Li Li; Hang Du; Chong Meng; Lin Fan; Hang Liu; Xu Han; Tanxi Ge; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2025)

Spatio-temporal coupling coordination analysis between local governments' environmental performance and listed companies' ESG performance - Xia Wu; Chunxu Hao; Yuhan Li; Chazhong Ge; Xianming Duan; Jing Ren; Cong Han (Environmental Impact Assessment Review, 2025)

Preparation of a novel organic-inorganic composite sludge bioflocculant (SBF) from dewatered sludge as raw material: Characteristics, flocculation mechanism and application for domestic sewage - Jingyun Ge; Hongyu Tian; Lin Li; Yunping Han; Jianwei Liu (Bioresource Technology, 2025)

Green hydrogen and porous carbon materials co-harvested through CO2-steam co-mediated gasification - Xin Zhang; Chuan Qin; Yi Lu; Quan Liu; Hongkang Liu; Chun Wang; Guanyu Zhang; Ge Kong; Kejie Wang; Jing Li; Jianying Shang; Xuesong Zhang; et al. (Bioresource Technology, 2025)

Exploring the seasonal characteristics of the equatorial Atlantic SSTA: insights from an extended recharge-discharge oscillator framework - Zhenyu Cai; Han-Ching Chen; Wenchang Ge; Leishan Jiang (Climate Dynamics, 2025)

Integrated transcriptomic and metabolomic analysis reveals weak anti-feeding capability from submerged plant Ottelia alismoides to freshwater snails - Ye Liu; Yu Cao; Wei Li; Hongsheng Jiang; Jiwen Ge; Charity Mangoi; Qingxiang Han (Aquatic Botany, 2025)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Influence of climate and landscape structure on soil erosion in China’s Loess Plateau: Key factor identification and spatiotemporal variability - Guanglei Li; Han Wang; Shouguo Zhang; Chang Ge; Jiansheng Wu (Science of The Total Environment, 2024)

Analysis on pollutants removal and sludge characteristics of a novel two-phase anaerobic/aerobic/integrated deoxygenated and anoxic reactor associated with membrane process for treating pesticide wastewater - Shuya Zhuang; Zhaobo Chen; Zhibo Liang; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Science of The Total Environment, 2024)

RETRACTED: Physicochemically protected organic carbon release is the rate-limiting step of rhizosphere priming in paddy soils - Cuiyan Wu; Wei Huang; Yixian Liu; Han Li; Shuai Ding; Zhenke Zhu; Feng Wang; Feike A. Dijkstra; Guangbin Zhang; Yakov Kuzyakov; Weiguo Cheng; Mouliang Xiao; et al. (Science of The Total Environment, 2024)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

Associations between magnesium depletion score and depression among individuals aged 20 to 60 years - Zongao Cai; Jiachen She; Xiaozhu Liu; Ruihui Li; Shuang Guo; Zeyang Han; Jiyang Zhou; Hairong Zhang; Yudi Xu; Ge Zhang; Zhaokai Zhou; Xueli Guo; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Model the evolutionary pattern of N species and pool size in groundwater continuum by utilizing measured source and sink rates of nitrate and ammonium - Li-Li Han; Lianghao Ge; Ehui Tan; Wenbin Zou; Li Tian; Ping Li; Min Nina Xu; Shuh-Ji Kao (Journal of Hazardous Materials, 2024)

Effect of rosemary extract on volatile flavor profile and flavor source of skipjack tuna - Jiaqi Liu; Ge Han; Yue Wang; Yidan Wang; Zhengqi Liu; Xiuping Dong (Food Bioscience, 2024)

A novel and cost-effective biological denitrification associated with membrane process for treating pesticide wastewater: Excellent nitrogen removal effect and higher environment benefits - Shuya Zhuang; Dongxue Hu; Zhaobo Chen; Zhibo Liang; Junzhe Song; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Jitao Yan; Yifan Wang; Shiming Cui (Desalination, 2024)

Tough polyacrylic acid hydrogels with stable swelling and active functionalities enabled by quaternized cellulose nanofibrils and iron ions for absorbent pad interlayers - Wenjiao Ge; Shan Cao; Han Yu; Xiaohui Wang (Carbohydrate Polymers, 2024)

Mangrove fungi in action: Novel bioremediation strategy for high-chloride wastewater - Zhiping Han; Edward S.X. Moh; Xin Ge; Xingqian Luo; Haizhou Wang; Jie Ma; Sien Shi; Jianzhi Ye (Bioresource Technology, 2024)

Spatial heterogeneity of volatile organic compound pollution in a typical industrial park based on multi-point online monitoring: Pollution characteristics, health risks, and priority-controlled species - Mengjuan Han; Ge Ren; Xinna Zhao; Xiaodong Zhang; Hong Lin; Dan Liu; Lei Wang (Atmospheric Environment, 2024)

Confirming the enzymatic activity and neurodevelopmental trajectory of PYCR1 mutation in one child with autosomal-recessive cutis laxa type 2 - Shaofang Shangguan; Xueyuan Zhang; Yangyang Ge; Ye Han; Ling Xiao; Yu Zhang; Hua Xie; Xiaoli Chen; Xiaoyan Wang (Molecular Genetics and Genomics, 2024)

The ABC1K gene family in Chinese cabbage: phylogeny, structure and function - Yuanxin Ye; Hengwu Ding; De Bi; Wen Ge; Jianke Yang; Shiyun Han; Sijia Zhang; Yuhong Liu; Xianzhao Kan (Genetic Resources and Crop Evolution, 2024)

Efficient RNA interference method by feeding in Brachionus plicatilis (Rotifera) - Yu Zhang; Dongqi Kan; Yang Zhou; Hairong Lian; Lingling Ge; Jing Shen; Zhongqi Dai; Yan Shi; Cui Han; Xiaojie Liu; Jiaxin Yang (Biotechnology Letters, 2024)

Identification of SNPs and Candidate Genes Associated with Growth Using GWAS and Transcriptome Analysis in Portuguese Oyster (Magallana angulata) - Jingyi Xie; Yue Ning; Yi Han; Caiyuan Su; Xiaoyan Zhou; Qisheng Wu; Xiang Guo; Jianfei Qi; Hui Ge; Yizou Ke; Mingyi Cai (Fishes, 2024)
Portuguese oyster (Magallana angulata) is one of the most important shellfish species worldwide. Although significant improvements in growth have been achieved through artificial selection breeding, the genetic basis underlying these traits remains unclear. Thus, this study aimed to (i) estimate variation and heritability for growth-related traits and (ii) identify SNPs and candidate genes associated with growth traits in Portuguese oyster. Five growth-related traits, including shell height (SH), shell length (SL), shell width (SW), whole weight (WW), and soft tissue weight (STW), were measured and analyzed in 114 one-year-old individuals from a cultivated population in Fujian Province, China. Through whole-genome sequencing and genotyping, we obtained 8,183,713 high-quality SNPs. Based on the genomic relationship matrix, heritability for the five traits was estimated, ranging from 0.071 to 0.695. Through genome-wide association analysis (GWAS), a total of nine SNPs were identified as significantly or suggestively associated with one of the growth-related traits, each explaining phenotypic variation ranging from 14.13% to 18.56%. Differentially expressed genes (DEGs) between individuals with extreme phenotypes were identified using comparative transcriptome analysis, ranging from 868 to 2274 for each trait. By combining GWAS and comparative transcriptome analysis, a total of seven candidate genes were identified, with biological functions related to growth inhibition, stress response, cell cycle regulation, and immune defense. The associations between the candidate genes and the growth-related traits were validated by using single-marker association analysis in other populations. Based on SNPs in these candidate genes, 16 haplotypes associated with growth-related traits were obtained. This study contributes to a deeper understanding of the genetic mechanisms of growth traits, and provides a theoretical basis and genetic markers for the breeding of fast-growing strains of the Portuguese oyster.

Exploring the Updated Roles of Ferroptosis in Liver Diseases: Mechanisms, Regulators, and Therapeutic Implications - Ting Ge; Yang Wang; Yiwen Han; Xiaofeng Bao; Chunfeng Lu (Cell Biochemistry and Biophysics, 2024)

PRRSV infection inhibits CSFV C-strain replication via GSDMD-mediated pyroptosis - Ruijiao Jiang; Dengjin Chen; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Structural determinants of parabens in inhibiting human and rat gonadal 3β-hydroxysteroid dehydrogenase - Chentao Ding; He Zhu; Yunbing Tang; Yingfen Ying; Yang Zhu; Han Lin; Ren-Shan Ge; Huitao Li (Toxicology and Applied Pharmacology, 2024)

Quantifying CO2 emissions of power plants with Aerosols and Carbon Dioxide Lidar onboard DQ-1 - Ge Han; Yiyang Huang; Tianqi Shi; Hongyuan Zhang; Siwei Li; Haowei Zhang; Weibiao Chen; Jiqiao Liu; Wei Gong (Remote Sensing of Environment, 2024)

Mechanism study on the synergistic degradation of DMAC wastewater by electrocatalytic carbon membrane reactor coupled with persulfate dual catalysis - Hong Wang; Jing Han; Minghui Du; Zhaohui Yin; Qingqing Wang; Xiaolong Ge; Zhen Yin; Jianxin Li (Journal of Water Process Engineering, 2024)

The effect of pre-existing structures on the Cenozoic rifting processes: Insights from seismic reflection imaging of the northeastern south China sea - Zongdong Pan; Shaoping Lu; Hongfang Gao; Qing He; Han Chen; Xiao Ge (Journal of Structural Geology, 2024)

Effect of climate warming on subsurface temperature in basins with topography-driven groundwater flow - Yi-Peng Zhang; Xiao-Wei Jiang; Shemin Ge; Zhi-Yuan Zhang; Peng-Fei Han; Xu-Sheng Wang; Lizhi Wang; Qing Liu; Li Wan (Journal of Hydrology, 2024)

Spatiotemporal analysis of the food-related carbon emissions of China: Regional heterogeneity and the urban‒rural divide - Jinyu Han; Jiansheng Qu; Tek Narayan Maraseni; Jingjing Zeng; Dai Wang; Yujie Ge; Dingye Wu (Journal of Environmental Management, 2024)

Analysis of canopy interception characteristics and influencing factors in typical artificial forest in the Loess Plateau semi-arid region - Yuanhao Liu; Fei Wang; Shuyu Zhang; Wenbin Ding; Rongqi Li; Jianqiao Han; Wenyan Ge; Hao Chen; Shangyu Shi (Journal of Environmental Management, 2024)

Heterogeneous marine response during the Toarcian Oceanic Anoxic Event (TOAE): The potential role of storminess - Yuzhu Ge; Zhong Han; Thomas J. Algeo; David B. Kemp; Luya Wu (Global and Planetary Change, 2024)

Serum levels of perchlorate and chlorate in pregnant women from south China and the related health risk with thyroid function - Yining Chen; Han Zhang; Shaoyou Lu; Yiming Ge; Jiajia Ji; Tao Chen (Food and Chemical Toxicology, 2024)

Effects of nitrile compounds on the structure and function of soil microbial communities as revealed by metagenomes - Ting Gao; Yiwang Wang; Jinlong Lai; Fuli Wang; Ge Yao; Shaoheng Bao; Jiajia Liu; Xiukun Wan; Chang Chen; Yunfei Zhang; Hui Jiang; Shijie Jiang; et al. (Environmental Research, 2024)

Parabens, bisphenols, and triclosan in coral polyps, algae, and sediments from sanya, China: Occurrence, profiles, and environmental implications - Yiming Ge; Han Zhang; Jinfeng Fu; Zhihui Guo; Qiulu Dong; Jiaxin Yu; Zhiling Mo; Yuxi Lai; Jialei Yang; Shaoyou Lu (Environmental Pollution, 2024)

Global hydroclimate perturbations during the Toarcian oceanic anoxic event - David B. Kemp; Zhong Han; Xiumian Hu; Wenhan Chen; Simin Jin; Kentaro Izumi; Qing Yan; Viktória Baranyi; Xin Jin; Jacopo Dal Corso; Yuzhu Ge (Earth-Science Reviews, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Anionic and cationic co-doping to enhance the oxygen transport property of Bi0.5Sr0.5FeO3-δ as a high-performance air electrode for reversible solid oxide cells - Hui Ye; Yixuan Feng; Pengkai Shan; Bin Qian; Lin Ge; Han Chen; Yifeng Zheng (Chemical Engineering Journal, 2024)

Inhibition of human and rat placental 3β-hydroxysteroid dehydrogenases by bisphenol A analogues depends on their hydrophobicity: In silico docking analysis - Shaowei Wang; Han Lu; Yingna Zhai; Yunbing Tang; Ming Su; Huitao Li; Yiyan Wang; Yi Liu; Ren-shan Ge (Chemico-Biological Interactions, 2024)

Identifying modifiable factors and their joint effect on frailty: a large population-based prospective cohort study - Ling-Zhi Ma; Yi-Jun Ge; Yi Zhang; Xi-Han Cui; Jian-Feng Feng; Wei Cheng; Lan Tan; Jin-Tai Yu (GeroScience, 2024)

Anaerobic degradation of pesticide wastewater: Improving sludge characteristics and reducing membrane fouling with combined tandem UASB+membrane system with high velocity settlers - Jitao Yan; Zhaobo Chen; Dongxue Hu; Hui Ge; Bei Jiang; Jian Dong; Fei Han; Shuya Zhuang; Zhibo Liang; Yifan Wang; Shiming Cui (Water Research, 2024)

Sediment porewaters serve as a transient organic carbon pool at the land-ocean interface - Kang Li; Bin Zhao; Lulu Han; Tiantian Ge; Nan Wang; Peng Yao (Water Research, 2024)

Investigation of canopy interception characteristics in slope protection grasses: A laboratory experiment - Xu-Guang Gao; Ji-Peng Wang; Shangqi Ge; Shuai-Kang Su; Mo-Han Bai; Bertrand Francois (Science of The Total Environment, 2024)

Upcycling of medical protective clothing for H2 production through catalytic steam reforming over Ni-impregnated catalysts - Kejie Wang; Jiajia Yu; Fangqi Liu; Jin Wang; Ge Kong; Guanyu Zhang; Suan Shi; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2024)

Crosslinking ability of hydrolyzed distarch phosphate and its stabilizing effect on rehydrated sea cucumber - Jiaqi Yu; Wenhao Ge; Kaifeng Wang; Wenhui Hao; Shangju Yang; Ying Xu; Tingyu Feng; Peng Han; Xun Sun (Food Chemistry, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

A pH-responsive MOFs@MPN nanocarrier with enhancing antifungal activity for sustainable controlling myclobutanil release - Yushan Hou; Yaowei Zhang; Yanyan Huang; Ailing Zhou; Jiatong Han; Kexin Yang; Yiming Zhao; Jie Zhou; Jing Wang; Ge Chen; Xiaomin Xu; Donghui Xu; et al. (Chemical Engineering Journal, 2024)

Smart contact Lenses: From rational design strategies to wearable health monitoring - Fei Han; Ping Ge; Fei Wang; Yanshen Yang; Shumeng Chen; Jing Kang; Yuan Ren; Hao Liu; Zhao Wei; Yuan He; Feng Xu (Chemical Engineering Journal, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Enhancing soil particle content prediction accuracy: advanced hyperspectral analysis and machine learning models - Xiao Wang; Jianli Ding; Lijing Han; Jiao Tan; Xiangyu Ge (Journal of Soils and Sediments, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Small-strain stiffness of compacted loess upon wetting, drying and loading: Experiments and model interpretation - Miaomiao Ge; Xiaona Han; Rui Yang; Caihui Zhu (Transportation Geotechnics, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Effect of vegetation on unsaturated soil hydraulic and the slope stability under rainfall - Ji-Peng Wang; Mo-Han Bai; Yi-Ran Tan; Shangqi Ge; Xu-Guang Gao; Abdelali Dadda; Jing-Yi Shen; Jiong Zhang (Rhizosphere, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Perchlorate in foodstuffs from South China and its implication for human dietary exposure - Yining Chen; Han Zhang; Yiming Ge; Zhou Zhu; Jiajia Ji; Donghui Luo; Shaoyou Lu (Food and Chemical Toxicology, 2024)

Bamboo-inspired lightweight, mechanically-stable and vibration-damping structural members for engineering applications - Shanyu Han; Deyue Li; Fuming Chen; Mingqian Wang; Yubing Leng; Yanjun Li; Hanzhou Ye; Ge Wang (Engineering Structures, 2024)

Optimization of ethylene thiourea, cyanide, and heavy metals removal and gas production enhancement in organosulfur pesticide wastewater using ferromagnetic biochar in anaerobic membrane bioreactor - Yifan Wang; Zhaobo Chen; Dongxue Hu; Liwen Jiang; Shiming Cui; Shuya Zhuang; Jitao Yan; Jian Dong; Fei Han; Bei Jiang; Hui Ge; Zhibo Liang (Chemical Engineering Journal, 2024)

Machine-learning-assisted n-GaN-Au/PANI gas sensor array for intelligent and ultra-accurate ammonia recognition - Dan Han; Yu Wang; Yuxuan Wang; Qi Duan; Donghui Li; Yang Ge; Xiuli He; Li Zhao; Weidong Wang; Shengbo Sang (Chemical Engineering Journal, 2024)

Genistein-3′-sodium sulfonate promotes brain functional rehabilitation in ischemic stroke rats by regulating astrocytes polarization through NF-κB signaling pathway - Ruizhen Liu; Yunling Yu; Qinglian Ge; Ruixue Feng; Guixiang Zhong; Li Luo; Zun Han; Tianyun Wang; Cheng Huang; Jinhua Xue; Zhihua Huang (Chemico-Biological Interactions, 2024)

A novel compound heterozygous mutation of UFC1 in a patient with neurodevelopmental disorder - Ye Han; Yangyang Ge; Haoran Liu; Liying Liu; Lina Xie; Xiaoli Chen; Qian Chen (Genes & Genomics, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

The accumulation of cadmium and lead in wheat grains is primarily determined by the soil-reducible cadmium level during wheat tillering - Jing Wang; Tengyun Zhang; Jianlei Gao; Bei Li; Long Han; Wenjing Ge; Zongyao Wang (Chemosphere, 2024)

Complete genome sequence of a novel Pseudomonas sp. IT1137 isolated from Antarctic intertidal sediment showing potential for alkane degradation at low temperatures - Hui-Yan Ge; Yi-He Zhang; Yong-Qiang Hu; Wei Han; Yu Du; Ting Hu; Yin-Xin Zeng (Marine Genomics, 2024)

Effect of inorganic anions on quinoline removal by catalytic ozonation: Performance and mechanism - Zhaochang Wu; Sijie Ge; Ying Han; Mengchen Zong; Shilong He; Jie Zhang (Journal of Environmental Chemical Engineering, 2024)

Upcycling heteroatoms-containing plastics via bimetallic synergistic catalysis: Unveiling the role of O and Cl in C-H bond cleavage - Yuan Jiang; Guanya Ji; Fangqi Liu; Ge Kong; Linling Zhou; Guanyu Zhang; Kejie Wang; Xuesong Zhang; Lujia Han (Chemical Engineering Journal, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Transformation of regional vegetation driven by climate change during the last deglacial–early Holocene at Chaohu Lake, eastern China: New pollen insights - Xiaoyu Han; Junwu Shu; Li Wu; Baohua Li; Shuguang Lu; Wei Chen; Jinglian Ge (Review of Palaeobotany and Palynology, 2024)

Central Asia's desertification challenge: Recent trends and drives explored with google earth engine - Shuang Zhao; Jianli Ding; Jinjie Wang; Xiangyu Ge; Lijing Han; Ruimei Wang; Shaofeng Qin (Journal of Cleaner Production, 2024)

A model coupling ecological and hydrodynamic processes for simulating the biogeomorphology of a coastal salt marsh - Ke-Hua Zhu; Jian Zeng; Zhen-Ming Ge; Yin Zuo; Shi-Hua Li; Lei-Hua Zhao; Yu Han; Hai-Feng Cheng; Pei Xin (Ecological Modelling, 2024)

UV-filter benzophenones suppress human, pig, rat, and mouse 11β-hydroxysteroid dehydrogenase 1: Structure-activity relationship and in silico docking analysis - Ting Hao; Xin Zhao; Zhongyao Ji; Miaomiao Xia; Han Lu; Jianmin Sang; Shaowei Wang; Linxi Li; Ren-shan Ge; Qiqi Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Performance of a novel up-flow electrocatalytic hydrolysis acidification reactor (UEHAR) coupled with anoxic/oxic system for treating coking wastewater - Jian Dong; Zhaobo Chen; Fei Han; Dongxue Hu; Hui Ge; Bei Jiang; Jitao Yan; Shuya Zhuang; Yifan Wang; Shiming Cui; Zhibo Liang (Water Research, 2024)

Significant influence of urban human activities and marine input on rainwater chemistry in a coastal large city, China - Jie Zeng; Guilin Han; Qixin Wu; Rui Qu; Qing Ma; Jingwen Chen; Shijun Mao; Xin Ge; Zhong-Jun Wang; Zhiheng Ma (Water Research, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Occupant behavioral adjustments and thermal comfort with torso and/or foot warming in two cold indoor environments - Faming Wang; Ying Ke; Qing Zheng; Xin'ge Han; Wei Su; Xiang Zhang; Tze-Huan Lei; Zhou Sun; Haiyan Zhou; Bin Yang (Building and Environment, 2024)

Machine learning elucidates ubiquity of enhanced ozone air pollution in China linked to the spring festival effect - Baizhen Zhu; Jie Fang; Yunjiang Zhang; Jian Qiu; Kehong Chen; Kexin Zhang; Hongwei Liang; Han Yang; Yihua Ding; Xinlei Ge (Atmospheric Pollution Research, 2024)

Hydrogen-bond tuned conjugated architectures for nitric oxide sensing in single-benzene framework: Advances and mechanistic insights - Feng-Zao Chen; Cun-Bin Du; Yi-Chao Wang; Jie Zhu; Ge Cheng; Kai-Bin Li; De-Man Han; Xiao-Yu Wu (Analytica Chimica Acta, 2024)

Enhanced lipid productivity of Monoraphidium strains in co-cultures and their potential for biodiesel production - Yimeng Lin; Jing Xu; Jixin Liu; Han Wang; Jingping Ge; Wenxiang Ping (Algal Research, 2024)

Glacial activity and paleoclimatic evolution records in the Cosmonaut Sea since the last glacial maximum - Dong Chen; Qian Ge; Ziyan Lei; Bingfu Zhou; Xibin Han (Frontiers in Marine Science, 2024)
This research explored the origin and paleoenvironmental significance of sediments from the Cosmonaut Sea, Antarctica, focusing on the period since the Last Glacial Maximum (LGM, 26,000 cal a BP). Sediment samples from core ANT37-C5/6-07 were subjected to AMS 14 C dating, clay-mineral assemblage analysis, grain size evaluation, and geochemical testing. Results indicated illite as the dominant clay mineral (average 46%), followed by kaolinite (22%) and smectite (21%), with chlorite (11%) being the least abundant. Comparison with previous studies suggested that these sediments are largely derived from weathered material from Prydz Bay and Enderby Land coastal regions. The study of mineral ratios, geochemical elements, and sediment grain size, alongside δ 18 O values from the East Antarctica EDML ice core, revealed that the ice sheet in the study area retreated around 18600 cal a BP, melted more markedly during 16800-15000 cal a BP, tended to expand during 14800-13500 cal a BP, and then the ice sheet remained in a state of retreat until it expanded again around 5000 cal a BP. It is largely synchronous with the phased changes in the Antarctic climate since the LGM (26ka) of the Cosmonaut Sea. Notably, the sediment record aligns with major paleoclimatic events, including Heinrich Stadial 1 and the Younger Dryas in the northern hemisphere and the Antarctic cold reversal, reflecting a climatic ‘seesaw’ effect. These findings suggest that the sedimentary record in the Cosmonaut Sea is a sensitive indicator of climatic conditions, highlighting a history of glacial movements and revealing East Antarctica’s climatic fluctuations. Additionally, the research indicates that the regional ice sheet is more sensitive to climatic changes than previously believed, underscoring its instability.

Digital carbon neutrality: evidence of carbon emission reduction based on digital inclusive finance - Jianyu Han; Weihong Liang; Jiamin Ge (Environmental Science and Pollution Research, 2024)

Evolution and determinants of precipitation chemistry in a plateau city, China: Insight from the pollutants source identification and environmental effect - Jie Zeng; Guilin Han; Qixin Wu; Qing Ma; Shijun Mao; Xin Ge; Zhong-Jun Wang; Chao Yang (Urban Climate, 2024)

Research progress on improving the freeze-drying resistance of probiotics: A review - Sitong Ge; Jiarun Han; Qiaoyu Sun; Qingqing Zhou; Zhongdu Ye; Ping Li; Qing Gu (Trends in Food Science & Technology, 2024)

Investigation of dry environment construction Equipment's medium displacement system for submarine pipelines - Kaichuang Wang; Jiawang Chen; Jian Huang; Peiwen Lin; Jin Guo; Hai Zhu; Yuping Fang; Xuehua Chen; Guomin Cao; Wenbao Jia; Xu Gao; Han Ge (Ocean Engineering, 2024)

Changes in preferential flow caused by root effects in black locust plantations of different stand ages in the semi-arid region of the Loess Plateau - Lu Cai; Fei Wang; Yuanyuan Lin; Qi Long; Yulong Zhao; Jianqiao Han; Wenyan Ge; Hao Chen (Journal of Hydrology, 2024)

China's “coal-to-gas” policy had large impact on PM1.0 distribution during 2016–2019 - Tianqi Shi; Yanran Peng; Xin Ma; Ge Han; Haowei Zhang; Zhipeng Pei; Siwei Li; Huiqin Mao; Xingying Zhang; Wei Gong (Journal of Environmental Management, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Green manure substitution for potassium fertilizer promotes agro-ecosystem multifunctionality via triggering interactions among soil, plant and rhizosphere microbiome - Qing Zeng; Mei Yin; Li-Bo Fu; Brajesh K. Singh; Si-Yi Liu; Hua Chen; An-Hui Ge; Li-Li Han; Li-Mei Zhang (Plant and Soil, 2024)

Detoxification strategy of Microcystis aeruginosa to the toxicity of Cd(II): role of EPS in alleviating toxicity - Xingye Han; Fangyuan Liu; Yibo Zhang; Kai Cheng; Heyun Wang; Hongmei Ge (Journal of Oceanology and Limnology, 2024)

Revealing early Neolithic vegetation and environmental changes in the Lower Yangtze Valley, eastern China: Pollen insights - Jinglian Ge; Junwu Shu; Limi Mao; Xiaoyu Han; Yu Cheng (Review of Palaeobotany and Palynology, 2024)

Enhanced mixed flotation of copper–molybdenum ore using dodecyl dimethyl betaine-emulsified kerosene as environmentally friendly collector - Wencheng Ge; Jie Liu; Hui Ren; Yimin Zhu; Wenjie Han; Yuexin Han (Journal of Cleaner Production, 2024)

Biotransformation characteristics of tetracycline by strain Serratia marcescens MSM2304 and its mechanism evaluation based on products analysis and genomics - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yixuan Chen; Jun Meng (Journal of Environmental Management, 2024)

Demethoxylation of curcumin enhances its inhibition on human and rat 17β-hydroxysteroid dehydrogenase 3: QSAR structure-activity relationship and in silico docking analysis - Zhongyao Ji; Jianmin Sang; Hong Wang; Miaomiao Xia; Ting Hao; Liping Chen; Han Lu; Shaowei Wang; Ming Yao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2024)

Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2024)

Automatic identification of factor profiles can be achieved by improved machine learning model - Bo Xu; Junbo Huang; Yi Ge; Chun Zhang; Han Xu; Feng Wang; Huan Zhao; Linlin Zhang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Environment, 2024)

Spatial variations of DOM in a diverse range of lakes across various frozen ground zones in China: Insights into molecular composition - Zhidan Wen; Jiarui Han; Yingxin Shang; Hui Tao; Chong Fang; Lili Lyu; Sijia Li; Junbin Hou; Ge Liu; Kaishan Song (Water Research, 2024)

Contrasting responses of relationship between solar-induced fluorescence and gross primary production to drought across aridity gradients - Ruonan Qiu; Ge Han; Xing Li; Jingfeng Xiao; Jiangong Liu; Songhan Wang; Siwei Li; Wei Gong (Remote Sensing of Environment, 2024)

Preparation of lanthanum-modified bentonite and its combination with oxidant and coagulant for phosphorus and algae removal - Ge Han; Shenshen Cui; Zheng Fu; Xinshan Song; Xiaohua Chen; Yuhui Wang (Journal of Water Process Engineering, 2024)

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

Nonvisual system-mediated body color change in fish reveals nonvisual function of Opsin 3 in skin - Zihao Zhang; Chenchen Shi; Jian Han; Xiaoyu Ge; Na Li; Yang Liu; Jing Huang; Shixi Chen (Journal of Photochemistry and Photobiology B: Biology, 2024)

Enhanced inhibition of human and rat aromatase activity by benzene ring substitutions in bisphenol A: QSAR structure-activity relationship and in silico docking analysis - Jingyi Zheng; Sailing Chen; Han Lu; Miaomiao Xia; Shaowei Wang; Xiaoheng Li; Huitao Li; Yiyan Wang; Ren-shan Ge; Yi Liu (Journal of Hazardous Materials, 2024)

Upcycling of hazardous plastic waste by CO2 transformation-enhanced steam reforming over MgO-promoted Ni/C bifunctional catalyst - Xuesong Zhang; Kejie Wang; Fangqi Liu; Ge Kong; Guanya Ji; Yuan Jiang; Guanyu Zhang; Quan Liu; Qing Cheng; Tianqi Cao; Hongkang Liu; Xin Zhang; et al. (Chemical Engineering Journal, 2024)

OsGEX3 affects anther development and improves osmotic stress tolerance in rice - Han Bao; Yuchao Cui; Li Ge; Yan Li; Xiaorong Xu; Ming Tang; Yin Yi; Liang Chen (Planta, 2024)

Application of temperature-sensitive liquid embolic agent loaded with oxaliplatin in the TACE procedure for rabbit VX2 gastric cancer - Yahua Li; Xiaoyong Ge; Zongming Li; Zihe Zhou; Kunpeng Wu; Yifan Li; Tengfei Ji; Changran Wang; Kefeng Guo; Jianzhuang Ren; Xinwei Han; Kewei Ren (Drug Delivery and Translational Research, 2024)

A Study on the Assessment and Integration of Multi-Source Evapotranspiration Products over the Tibetan Plateau - Ming Cheng; Lei Zhong; Yaoming Ma; Han Ma; Yaoxin Chang; Peizhen Li; Meilin Cheng; Xian Wang; Nan Ge (Advances in Atmospheric Sciences, 2024)

Rice straw biochar and lime regulate the availability of heavy metals by managing colloid-associated- but dissolved-heavy metals - Hui Huang; Liang Ge; Xiaowei Zhang; Hangyu Chen; Yu Shen; Jian Xiao; Haiying Lu; Yongli Zhu; Jiangang Han; Ronghua Li (Chemosphere, 2024)

Variations in life history parameters, population dynamics, and transcriptome regulation of Brachionus plicatilis exposed to triclosan - YunhongYang; Tianyue Mao; Yifan Ding; Lingling Ge; Lei Feng; Meng Cai; Cui Han; Jiaxin Yang (Marine Pollution Bulletin, 2024)

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

Infection of PRRSV inhibits CSFV C-strain replication by inducing macrophages polarization to M1 - Tianbei Tuo; Dengjin Chen; Lihong Wang; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2024)

Chemical evolution of rainfall in China's first eco-civilization demonstration city: Implication for the provenance identification of pollutants and rainwater acid neutralization - Jie Zeng; Guilin Han; Qixin Wu; Meixue Peng; Xin Ge; Shijun Mao; Zhong-Jun Wang; Qing Ma (Science of The Total Environment, 2024)

Gallium extraction from red mud via leaching with a weak acid - Yimin Zhu; Wencheng Ge; Yu Zhang; Jie Liu; Wenjie Han; Qiang Zhang (Process Safety and Environmental Protection, 2024)

Changes in quality characteristics and metabolites composition of wheat under different storage temperatures - Yan Zhao; Ge Han; Yanfei Li; Haoxin Lv (Journal of Stored Products Research, 2024)

Nitrogen fertilization enhances organic carbon accumulation in topsoil mainly by improving photosynthetic C assimilation in a salt marsh - Juanyong Li; Yawen Chen; Tida Ge; Mingliang Zhao; Jiaxin Ge; Guangxuan Han (Journal of Environmental Management, 2024)

Calcium ions induced ι-carrageenan-based gel-coating deposited on zein nanoparticles for encapsulating the curcumin - Qingyuan Ge; Shuang Rong; Chenxi Yin; David Julian McClements; Qi Fu; Qi Li; Yahong Han; Fuguo Liu; Suqing Wang; Shuai Chen (Food Chemistry, 2024)

Chalcones from plants cause toxicity by inhibiting human and rat 11β-hydroxysteroid dehydrogenase 2: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Hang Lin; Ming Su; Chao Wen; Yunbing Tang; Huitao Li; Yandan Wu; Ren-shan Ge; Xing-wang Li; Han Lin (Food and Chemical Toxicology, 2024)

Machine learning-aided hydrothermal carbonization of biomass for coal-like hydrochar production: Parameters optimization and experimental verification - Quan Liu; Guanyu Zhang; Jiajia Yu; Ge Kong; Tianqi Cao; Guanya Ji; Xuesong Zhang; Lujia Han (Bioresource Technology, 2024)

The crosstalk between Toll and AMPK signaling pathways mediates growth inhibition of Eriocheir sinensis under deltamethrin stress - Qian Ren; Ximei Nie; Xingkong Ma; Zhengxiao Han; Yanfang Li; Xintong Yang; Lei Ji; Rongqian Su; Jiachun Ge; Xin Huang (Aquatic Toxicology, 2024)

Monoclonal Antibody Targeting CGRP Relieves Cisplatin-Induced Neuropathic Pain by Attenuating Neuroinflammation - Shun Xie; Zhenfang Gao; Jiale Zhang; Cong Xing; Yanxin Dong; Lanyin Wang; Zhiding Wang; Yuxiang Li; Ge Li; Gencheng Han; Taiqian Gong (Neurotoxicity Research, 2024)

Asiaticoside Attenuates Blood–Spinal Cord Barrier Disruption by Inhibiting Endoplasmic Reticulum Stress in Pericytes After Spinal Cord Injury - Zhenxin Hu; Tingting Wu; Ziheng Zhou; Yu Zhang; Qiyue Chen; Hanbing Yao; Mengchu Ji; Ge Shen; Chenling Dong; Chengge Shi; Zhixian Huang; Nizhou Jiang; et al. (Molecular Neurobiology, 2024)

Multiple Pathways for the Enhancement of Wheat Growth by Chlorella vulgaris - Sheng-Nan Wang; Shu-Han Ge; Lin-Lan Zhuang; Jian Zhang (Journal of Plant Growth Regulation, 2024)

Saturation Estimation with Complex Electrical Conductivity for Hydrate-Bearing Clayey Sediments: An Experimental Study - Lanchang Xing; Shuli Zhang; Huanhuan Zhang; Chenyutong Wu; Bin Wang; Liyun Lao; Wei Wei; Weifeng Han; Zhoutuo Wei; Xinmin Ge; Shaogui Deng (Journal of Ocean University of China, 2024)

Morphological and phylogenetic analyses reveal a new species of Anthracophyllum (Omphalotaceae, Agaricales) in Zhejiang Province, China - Wen-Juan Yang; Miao Xu; Jing Zhang; Fan Zhou; Zhi-Fang Le; Wen-Jun Tong; Hai-Yan Song; Zhuo-Han Jin; Qiu-Ge Cheng; Jian-Ping Zhou; Yang Gao; Zhi-Jun Zhai; et al. (Archives of Microbiology, 2024)

Proper C/N ratio enhances the effect of plant diversity on nitrogen removal and greenhouse effect mitigation in floating constructed wetlands - Chenxu Xiang; Yuanyuan Du; Wenjuan Han; Baohua Guan; Hua Liu; Yu An; Yu Liu; Hang Jiang; Jie Chang; Ying Ge (Environmental Science and Pollution Research, 2024)

Impact of circumpolar deep water on organic carbon isotopes and ice-rafted debris in West Antarctic: a case study in the Amundsen Sea - Ziyan Lei; Qian Ge; Dong Chen; Yongcong Zhang; Xibin Han (Frontiers in Marine Science, 2024)
This research delves into the interaction between carbon isotopes, ice-rafted debris (IRD), and Circumpolar Deep Water (CDW) in the Amundsen Sea, West Antarctic. Utilizing sediment core ANT36-A11-04, we traced the source of the organic matter though an analysis of the total organic carbon (TOC), stable carbon isotopes (δ 13 C org ), and nitrogen content. We identified six environmental events in this region since the Mid-Holocene, which were discerned through a comparative analysis of the δ 13 C org , TOC, and IRD content. These events were closely linked to variations in the intensity of the CDW. Notably, the synchronous occurrence of a negative shift in the δ 13 C org value and increases in TOC and IRD highlight the significant impact of CDW intrusion, underlining the pivotal role of the CDW in the regional environmental evolution. Specifically, intensified upwelling of the CDW was correlated with increased heat and nutrients, enhanced glacier melting, phytoplankton blooms, higher TOC content, augmented deposition of IRD, and finally resulted in a negative shift in the δ 13 C org value. We present a comprehensive picture of the local environmental evolution in the Amundsen Sea, characterized as a marine-glacial-biological coupling model, thereby contributing to a broader understanding of Antarctic environmental dynamics.

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

Impacts of electric field-magnetic powder coupled membrane bioreactor on phenol wastewater treatment: Performance, synergistic mechanism, antibiotic resistance genes, and eco-environmental benefit evaluation - Bei Jiang; Qianzhi Zeng; Qiangwei Liu; Huiying Chai; Jinxun Xiang; Hongxin Li; Shengnan Shi; Aifu Yang; Zhaobo Chen; Yubo Cui; Dongxue Hu; Hui Ge; et al. (Science of The Total Environment, 2024)

Continuous cropping disorders of eggplants (Solanum melongena L.) and tomatoes (Solanum lycopersicum L.) in suburban agriculture: Microbial structure and assembly processes - Zufei Xiao; Changyi Lu; Zhiyong Wu; Xinyuan Li; Kai Ding; Zhe Zhu; Ruixia Han; Junyi Zhao; Tida Ge; Gang Li; Yong-Guan Zhu (Science of The Total Environment, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Insight into the enhancement effect of humic acid on microbial degradation of triclosan in anaerobic sediments - Juan Chen; Bo Zhang; Chao Wang; Peifang Wang; Ge Cui; Han Gao; Bingbing Feng; Jingjing Zhang (Journal of Hazardous Materials, 2024)

Indoor air quality of urban public transportation stations in China: Based on air quality evaluation indexes - Lin Fan; Xu Han; Li Li; Hang Liu; Tanxi Ge; Xinqi Wang; Qin Wang; Hang Du; Liqin Su; Xiaoyuan Yao; Xianliang Wang (Journal of Environmental Management, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Integrated transcriptomic, proteomic and metabolomic analysis provides new insights into tetracycline stress tolerance in pumpkin - Jing Yu; Tao Han; Yingying Hou; Jinjin Zhao; Haiguang Zhang; Xinjie Wang; Shidong Ge (Environmental Pollution, 2024)

A wearable self-powered microneedle system based on conductive drugs for infected wound healing: A new electrical stimulation delivery strategy - Shanguo Zhang; Tianyi Jiang; Fang Han; Liangyu Cao; Ming Li; Zhenyou Ge; Haoxiu Sun; Hao Wu; Wenlong Wu; Nannan Zhou; Muhammad Luqman Akhtar; Hongyuan Jiang (Chemical Engineering Journal, 2024)

Deciphering the role of particulate organic matter in soil nitrogen transformation in rice–rapeseed and rice–wheat rotation systems - Rongyan Bu; Shang Han; Wenlong Cheng; Yue Wu; Shan Tang; Min Li; Hui Wang; Zibing Ge; Ji Wu (Applied Soil Ecology, 2024)

Effects of nutrients and light in aquatic habitat on the growth of Hydrocotyle vulgaris when expanded from terrestrial to aquatic habitat - Zhi-Huan Chen; Rui Zhang; Jun-Cai Xin; Zi-Han Qian; Shu-Jie Wang; Shang-Yan Qiu; Xue-Ge He; Chao Si (Aquatic Botany, 2024)

Community diversity and co-occurrence patterns of keratinophilic microorganisms in hospital garden soils - Yulian Ren; Zhiyuan Zhang; Chunbo Dong; Wei Ge; Zongqi Liang; Yanfeng Han (Pedobiologia, 2023)

The evolution of the majiang paleoreservoir, west margin of xuefeng uplift: Insights from in situ calcite U–Pb dating and bitumen and shale trace element analysis - Xiang Ge; Chuanbo Shen; Yuqi Han; Yi Zhang; Guanzhong Shi; Zhenmin Cao; Guangyou Zhu (Marine and Petroleum Geology, 2023)

Characteristics and health risk assessment of indoor and outdoor PM2.5 in a rural village, in Northeast of China: impact of coal and biomass burning - Ge Ma; Xiuqun Liu; Jingzhi Wang; Minrui Li; Zhibao Dong; Xiaoping Li; Lijun Wang; Yongming Han; Junji Cao (Environmental Geochemistry and Health, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Soil moisture dominates the variation of gross primary productivity during hot drought in drylands - Ruonan Qiu; Ge Han; Siwei Li; Feng Tian; Xin Ma; Wei Gong (Science of The Total Environment, 2023)

Catalytic hydrothermal co-liquefaction of sewage sludge and agricultural biomass for promoting advanced biocrude production - Guanyu Zhang; Quan Liu; Xintong Li; Ge Kong; Tianqi Cao; Qing Cheng; Ziyi Zhang; Xuesong Zhang; Lujia Han (Journal of Cleaner Production, 2023)

Bisphenol analogues inhibit human and rat 17β-hydroxysteroid dehydrogenase 1: 3D-quantitative structure-activity relationship (3D-QSAR) and in silico docking analysis - Sailing Chen; Shaowei Wang; Jingyi Zheng; Han Lu; Huiqian Chen; Yunbing Tang; Nan Wang; Yang Zhu; Yiyan Wang; Ping Duan; Ren-shan Ge (Food and Chemical Toxicology, 2023)

Improving hydrogen-rich gas production from biomass catalytic steam gasification over metal-doping porous biochar - Ge Kong; Quan Liu; Guanya Ji; Haoyang Jia; Tianqi Cao; Xuesong Zhang; Lujia Han (Bioresource Technology, 2023)

Machine learning reveals the effects of drivers on PM2.5 and CO2 based on ensemble source apportionment method - Han Xu; Yi Ge; Chun Zhang; Zhenyu Wang; Bo Xu; Huan Zhao; Junbo Huang; Gen Wang; Jinxing Liu; Yinchang Feng; Guoliang Shi (Atmospheric Research, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Paleoproductivity and deep-sea oxygenation in Cosmonaut Sea since the last glacial maximum: impact on atmospheric CO2 - Liangming Hu; Yi Zhang; Yizhuo Wang; Pengyun Ma; Wendong Wu; Qian Ge; Yeping Bian; Xibin Han (Frontiers in Marine Science, 2023)
The paleoproductivity in the Southern Ocean plays a crucial role in controlling the atmospheric CO 2 concentration. Here, we present the sediment record of gravity core ANT37-C5/6-07, which was retrieved from the Cosmonaut Sea (CS), Indian Ocean sector of the Southern Ocean. We found that the change in the oxygen concentration in the CS bottom water is strongly correlated with the atmospheric CO 2 fluctuations since the Last Glacial Maximum (LGM). Based on the change in the export production, we reconstructed the evolution history of the deep-water ventilation/upwelling in the study area. During the LGM, a large amount of respiratory carbon was stored in the deep Southern Ocean due to the effect of the low export productivity and restricted ventilation. The oxygen concentration was also low at this time. Despite the increase in paleoproductivity, the biological pump efficiency remained at a low level during the Last Deglaciation. Vast quantities of CO 2 were released into the atmosphere through enhanced upwelling. The recovery of ventilation during this period facilitated the supply of oxygen-rich surface water to the deep ocean. Moreover, signals were identified during the transitions between the Heinrich Stage 1 (HS1), Antarctic Cold Reverse (ACR), and Younger Drays (YD) periods. During the Holocene, the productivity increased overall, and the oxygen in the bottom water was consumed but still remained at a high level. This may have been caused by the enhanced ventilation and/or the prevalence of East Cosmonaut Polynya (ECP) near Cape Ann.

Study of filtration, digestion and absorption of Chlorella pyrenoidosa by juvenile Chinese mitten crab (Eriocheir sinensis) - Jiancheng Zeng; Jian Tian; Dongqi Kan; Cui Han; Xiaoqing Fei; Xingkong Ma; Zhihong Wang; Weijian Shen; Jiaxin Yang; Jiachun Ge (Aquaculture, 2023)

Optimization of ship routing and allocation in a container transport network considering port congestion: A variational inequality model - Lingpeng Meng; Hu Ge; Xudong Wang; Wei Yan; Chuanfeng Han (Ocean & Coastal Management, 2023)

Scale-dependent and driving relationships between spatial features and carbon storage and sequestration in an urban park of Zhengzhou, China - Xiaoli Jia; Haiting Han; Yuan Feng; Peihao Song; Ruizhen He; Yang Liu; Peng Wang; Kaihua Zhang; Chenyu Du; Shidong Ge; Guohang Tian (Science of The Total Environment, 2023)

CO2-mediated catalytic upcycling of plastic waste for H2-rich syngas and carbon nanomaterials - Xuesong Zhang; Yuan Jiang; Ge Kong; Quan Liu; Guanyu Zhang; Kejie Wang; Tianqi Cao; Qing Cheng; Ziyi Zhang; Guanya Ji; Lujia Han (Journal of Hazardous Materials, 2023)

Comprehensive investigation of milk oligosaccharides in different mammalian species and the effect of breed and lactation period on sheep milk oligosaccharides - Haiyan Wang; Minghui Zhang; Yucui Huo; Xiuxiu Cui; Rui He; Bei Han; Zhongfu Wang; Yuxuan Song; Xin Lv; Jing Zhang; Wupeng Ge (Food Research International, 2023)

Bio-inspired robust and highly thermal conductive BNNS/PBO nanofiber composite films with excellent thermal stability, wear resistance, and adjustable photothermal properties - Tingting Sun; Wenxin Cao; Kechen Zhao; Xiaolei Wang; Zhuochao Wang; Ge Gao; Zhijie Ye; Kunlong Zhao; Zhenhua Su; Bing Dai; Mingfu Zhang; Jiecai Han; et al. (Chemical Engineering Journal, 2023)

Mixotrophy, a more promising culture mode: Multi-faceted elaboration of carbon and energy metabolism mechanisms to optimize microalgae culture - Shengzhou Shan; Artem Yurevich Manyakhin; Chun Wang; Baosheng Ge; Jichang Han; Xuezhi Zhang; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Highly efficient endosperm and pericarp protoplast preparation system for transient transformation of endosperm-related genes in wheat - Shichen Han; Ge Qu; Xiaohui Li; Feixiong Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

A comprehensive investigation on source apportionment and multi-directional regional transport of volatile organic compounds and ozone in urban Zhengzhou - Xiaoxi Zeng; Mengjuan Han; Ge Ren; Gege Liu; Xiaoning Wang; Kailun Du; Xiaodong Zhang; Hong Lin (Chemosphere, 2023)

PRRSV inhibited the proliferation of CSFV by inducing IL-1β maturation via NLRP3 inflammasome activation - Dengjin Chen; Tianbei Tuo; Yongning Zhang; Lei Zhou; Xinna Ge; Jun Han; Xin Guo; Hanchun Yang (Veterinary Microbiology, 2023)

Improving quantification of methane point source emissions from imaging spectroscopy - Zhipeng Pei; Ge Han; Huiqin Mao; Cuihong Chen; Tianqi Shi; Keyi Yang; Xin Ma; Wei Gong (Remote Sensing of Environment, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Exploring the inter-decadal variability of soil organic carbon in China - Zipeng Zhang; Jianli Ding; Chuanmei Zhu; Jinjie Wang; Xiang Li; Xiangyu Ge; Lijing Han; Xiangyue Chen; Jingzhe Wang (CATENA, 2023)

A XCO Retrieval Algorithm Coupled Spatial Correlation for the Aerosol and Carbon Detection Lidar - Zhipeng Pei; Ge Han; Tianqi Shi; Xin Ma; Wei Gong (Atmospheric Environment, 2023)

The Analysis of Microbial Community Characteristics Revealed that the Pathogens of Leaf Spot of Rosa roxburghii Originated from the Phyllosphere - Yuxing Liu; Wei Ge; Chunbo Dong; Qiuyu Shao; Zhiyuan Zhang; Xiao Zou; Haiyan Hu; Yanfeng Han (Indian Journal of Microbiology, 2023)

Assembly Processes and Biogeographical Characteristics of Soil Bacterial Sub-communities of Different Habitats in Urban Green Spaces - Yulian Ren; Qiuyu Shao; Wei Ge; Xin Li; Haiyan Wang; Chunbo Dong; Yanwei Zhang; Sunil Kumar Deshmukh; Yanfeng Han (Current Microbiology, 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

The relative importance of environmental heterogeneity and dispersal limitation on spatial patterns of phytoplankton communities varies across seasons - Feiyang Ge; Bin Chen; Shaopeng Wang; Qianqian Zhou; Zhiyuan Ma; Guangcheng Chen; Weiwei Yu; Wenxuan Han; Senming Tang; Shangke Su; Dian Zhang; Wanting Zhang; et al. (Limnology and Oceanography, 2023)
Environmental heterogeneity and dispersal limitation structure community assembly, but there is limited knowledge on how their effects vary on temporal scale. This study compiled a series of data, including phytoplankton, seawater depth and chemistry from 104 sites, to explore the spatial patterns and their drivers of phytoplankton communities in the Beibu Gulf and adjacent waters, located in the northwestern South China Sea. Our results showed that (1) the beta diversity values ranged from 0.2 to 0.84 (0.5 average), and turnover dominated. (2) The relative contributions of environmental heterogeneity and dispersal limitation to beta diversity varied seasonally, wherein former dominated in summer and winter, latter dominated in spring and autumn. (3) Hydrologic distance, pH, alkalinity, and total nitrogen were the crucial factors shaping the beta diversity pattern. This study detailed the temporal variation of the relative roles of environmental heterogeneity and dispersal limitation in shaping the patterns of phytoplankton communities, which may reflect the dynamical nature of ocean, characterized by seasonal variation in wind and hydrology. It also clarified the intrinsic linkage between these two processes in the ocean, which provides a novel insight to understanding the ocean biogeography and informs decision making for area‐based marine biodiversity conservation.

Quantitative evaluation of drought risk related to vegetation productivity in China - Wenyan Ge; Xiuxia Li; Mengxia Xie; Bowen Yu; Juying Jiao; Jianqiao Han; Fei Wang (Journal of Hydrology, 2023)

Species identification of culinary spices with two-locus DNA barcoding - Meng-Yue Zhou; Ran-Ran Xing; Ke-Han Liu; Yi-Qiang Ge; Ying Chen (Food Control, 2023)

Dysfunction of the intestinal physical barrier in the intestinal inflammation of tongue sole, Cynoglossus semilaevis, induced by Shewanella algae infection - Zhuoran Han; Lunhua Ge; Siyi Wen; Jingfeng Sun (Fish & Shellfish Immunology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Radiative contributions of different cloud types to regional energy budget over the SACOL site - Meihua Wang; Jing Su; Ying Xu; Xinyi Han; Nan Peng; Jinming Ge (Climate Dynamics, 2023)

Specialist species of fungi and bacteria are more important than the intermediate and generalist species in near-urban agricultural soils - Yulian Ren; Wei Ge; Chunbo Dong; Haiyan Wang; Shui Zhao; Chenglong Li; Jinhui Xu; Zongqi Liang; Yanfeng Han (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

Leydig cell development in pubertal male rats is blocked by perfluorotetradecanoic acid through decreasing AMPK-mTOR-autophagy pathway - Yunbing Tang; Lei Shi; Shaowei Wang; Han Lu; Huitao Li; Jieqiang Lv; Ren-shan Ge; Yingfen Ying (Toxicology Letters, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Poly-γ-glutamic acid-producing Bacillus velezensis fermentation can improve the feed properties of soybean meal - Han Hu; Caiyun Wu; Fanglan Ge; Yao Ren; Wei Li; Jiao Li (Food Bioscience, 2023)

Performance analysis and multi-objective optimization of a poly-generation system based on PEMFC, DCMD and heat pump - Wanchao Zhu; Jitian Han; Yi Ge; Jinwen Yang; Wenxing Liang (Desalination, 2023)

Detection of a mid-Holocene climate event at 7.2 ka BP based on an analysis of globally-distributed multi-proxy records - Mei Hou; Wenxiang Wu; David J. Cohen; Zhaoqi Zeng; Han Huang; Hongbo Zheng; Quansheng Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

PAX5 aberrant expression incorporated in MIPI-SP risk scoring system exhibits additive value in mantle cell lymphoma - Xin Zhang; Yang Han; Yu Nie; Yujie Jiang; Xiaohui Sui; Xueling Ge; Fang Liu; Ya Zhang; Xin Wang (Journal of Molecular Medicine, 2023)

Seeing the forest and the trees: Holistic view of social distancing on the spread of COVID-19 in China - Danlin Yu; Yaojun Zhang; Jun Meng; Xiaoxi Wang; Linfeng He; Meng Jia; Jie Ouyang; Yu Han; Ge Zhang; Yao Lu (Applied Geography, 2023)

A Spatially Fair and Low Conflict Medium Access Control Protocol for Underwater Acoustic Networks - Maochun Zheng; Wei Ge; Xiao Han; Jingwei Yin (Journal of Marine Science and Engineering, 2023)
The large propagation delay in underwater acoustic networks results in spatial and temporal uncertainty between communication links. This uncertainty, in turn, leads to problems with spatial unfairness and packet collision in media access control (MAC) solutions. To address these issues, this research paper proposes a spatially fair and low-conflict media access control (SFLC-MAC) protocol. Within the protocol, a contention window spatial fairness adjustment strategy is designed, including random and fair states. Nodes autonomously adjust their contention states based on the perceived network information. Nodes in the fair state increase their listening time to ensure that nodes in the random state can successfully access the channel, thereby overcoming the fairness issues in channel access. A method based on postponing data packet transmission is proposed to avoid collisions between data packets and neighbors’ control packets. By scrutinizing the spatio-temporal constraints pertinent to these conflicts, the exact duration of the delay required for this method is ascertained. Simulation results demonstrate that SFLC-MAC effectively improves network throughput, reduces end-to-end delay, decreases network energy consumption, and enhances channel access fairness among nodes.

A weighted contextual active fire detection algorithm based on Himawari-8 data - Han Zhang; Lin Sun; Chunkai Zheng; Shuai Ge; Jinpeng Chen; Jiayin Li (International Journal of Remote Sensing, 2023)

Thermodynamic restrictions determine ammonia tolerance of methanogenic pathways in Methanosarcina barkeri - Yue Yi; Jan Dolfing; Ge Jin; XiaoYu Fang; WenHao Han; LaiYan Liu; YueQin Tang; Lei Cheng (Water Research, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Gasification integrated with steam co-reforming of agricultural waste biomass over its derived CO2/O2/steam-mediated porous biochar for boosting H2-rich syngas production - Xuesong Zhang; Ge Kong; Xin Zhang; Kejie Wang; Quan Liu; Suan Shi; Lujia Han (Journal of Environmental Chemical Engineering, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

Attenuated cooling effects with increasing water-saving irrigation: Satellite evidence from Xinjiang, China - Chao Zhang; Jinwei Dong; Guoyong Leng; Russell Doughty; Kun Zhang; Songjun Han; Geli Zhang; Xuezhen Zhang; Quansheng Ge (Agricultural and Forest Meteorology, 2023)

Monitoring canopy-scale autumn leaf phenology at fine-scale using unmanned aerial vehicle (UAV) photography - Wenyan Ge; Xiuxia Li; Linhai Jing; Jianqiao Han; Fei Wang (Agricultural and Forest Meteorology, 2023)

Reassessing the age of the Early Pleistocene Longgupo fauna, southern China: An updated magnetostratigraphic perspective - LU SUN; CHENGLONG DENG; CAICAI LIU; JUNYI GE; SHIXIA YANG; SHUAI ZHANG; FEI HAN; JEAN‐JACQUES BAHAIN; MICHEL RASSE; ÉRIC BOËDA; YAMEI HOU; GUANGBIAO WEI; et al. (Journal of Quaternary Science, 2023)
As the northernmost locality yielding one of the most representative Early Pleistocene Gigantopithecus – Sinomastodon faunas in southern China, the Longgupo site has preserved valuable geological archives that have significantly improved our understanding of Pleistocene biostratigraphy and biogeography. A convincing chronological framework of this locality is therefore important to elaborate on the evolution of Quaternary faunas as well as paleoenvironment. To reconcile the existing geochronological results with new advances in geochronology and biochronology, we present here a revised magnetostratigraphic age model based on detailed rock magnetic and paleomagnetic data and strengthened by biochronology as well as recently published electron spin resonance and uranium series (ESR/U‐series) age data. Two geomagnetic polarities were identified from the Longgupo sequence: the upper one is thin and normal, corresponding to the Olduvai normal subchron; and the lower one is distinctly thick and reversed, corresponding to the pre‐Olduvai Matuyama Chron. The age of the Longgupo fauna constrained by this refined magnetochronological framework is therefore estimated to be about 2.5–2.0 Ma, consistent with the newly published ESR/U‐series age of 2.5–2.2 Ma.

Sources and spatial variations of heavy metals in offshore sediments of the western Pearl River Estuary - Jianru Zhao; Kehong Yang; Fengyou Chu; Qian Ge; Dong Xu; Xibin Han; Liming Ye (Marine Pollution Bulletin, 2023)

Transition of source/sink processes and fate of ammonium in groundwater along with redox gradients - Li-Li Han; Helin Wang; Lianghao Ge; Min Nina Xu; Jin-Ming Tang; Li Luo; Ping Li; Shuh-Ji Kao (Water Research, 2023)

Transcriptomic analysis of polyketide synthesis in dinoflagellate, Prorocentrum lima - Xiukun Wan; Ge Yao; Kang Wang; Shaoheng Bao; Penggang Han; Fuli Wang; Tianyu Song; Hui Jiang (Harmful Algae, 2023)

Bifunctional carbon nanofibrous interlayer embedded with cobalt single atoms for polysulfides trapping and catalysis in lithium-sulfur batteries - Beibei Song; Haoyue Zhao; Gang Zhao; Han Li; Can Ge; Guilong Yan; Jian Fang (Chemical Engineering Journal, 2023)

Toward high-performance dibenzo[g,p]chrysene-based conjugated polymer photocatalysts for photocatalytic hydrogen production through donor-acceptor-acceptor structure design - Peixuan Xie; Changzhi Han; Sihui Xiang; Shenglin Jin; Mantang Ge; Chong Zhang; Jia-Xing Jiang (Chemical Engineering Journal, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Trace elements in outdoor and indoor PM2.5 in urban schools in Xi’an, Western China: characteristics, sources identification and health risk assessment - Runyu Wang; Xinxin Ding; Jingzhi Wang; Zhibao Dong; Hongmei Xu; Ge Ma; Bo Gao; Han Song; Menghan Yang; Junji Cao (Environmental Geochemistry and Health, 2023)

Characterizing spatial, diurnal, and seasonal patterns of agricultural irrigation expansion-induced cooling in Northwest China from 2000 to 2020 - Chao Zhang; Quansheng Ge; Jinwei Dong; Xuezhen Zhang; Yan Li; Songjun Han (Agricultural and Forest Meteorology, 2023)

Decoupling of N and P aggravated upward along food chains in an urban river ecosystem - Shenqun An; Zhengbing Yan; Ying Song; Qiang Fu; Feiyang Ge; Zehao Wu; Wei An; Wenxuan Han (Chemosphere, 2023)

Imbalanced phytoplankton C, N, P and its relationship with seawater nutrients in Xiamen Bay, China - Xiaoqian Lu; Weiwei Yu; Bin Chen; Zhiyuan Ma; Guangcheng Chen; Feiyang Ge; Shenqun An; Wenxuan Han (Marine Pollution Bulletin, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Reclaimed water use improved polluted water's self-purification capacity --Evidenced by water quality factors and bacterial community structure - Shenqun An; Ying Song; Qiang Fu; Rong Qi; Zehao Wu; Feiyang Ge; Xiaoqian Lu; Wei An; Wenxuan Han (Journal of Cleaner Production, 2023)

Mn-induced strengthening hybridization effect of Co–O bond for stable oxygen evolution in acidic media - Ruo-Yao Fan; Hui-Ying Zhao; Yi-Nuo Zhen; Feng-Ge Wang; Han Hu; Yong-Ming Chai; Bin Dong (Fuel, 2023)

Perspective: Blinded by the bright—afforestation is affecting widespread sampling deficiency in plant collections - Yu Zhang; Meng-Ge Duan; Pei-Han Huang; Min Li; Hong-Hu Meng; Hui-Jie Qiao; Jie Li (Forest Ecology and Management, 2023)

Direct Z-scheme heterojunction of PCN-222/CsPbBr3 for boosting photocatalytic CO2 reduction to HCOOH - Peng Wang; Xiaohua Ba; Xiaowei Zhang; Hongyi Gao; Mengyi Han; Zhiyong Zhao; Xiao Chen; Linmeng Wang; Xuemei Diao; Ge Wang (Chemical Engineering Journal, 2023)

Role of mesoscale structure in gas–solid fluidization: Comparison between continuum and discrete approaches - Lina Yang; Caixia Han; Ji Xu; Bona Lu; Youhao Xu; Wei Wang; Wei Ge (Chemical Engineering Journal, 2023)

Dual metal-organic frameworks-derived Fe-atomic sites bounded to fine Fe/Fe C nanoparticles for enhanced oxygen electroreduction - Meixin Chen; Fantao Kong; Heliang Yao; Yafeng Chen; Ge Meng; Ziwei Chang; Chang Chen; Han Tian; Lianzhou Wang; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2023)

Impact of flow velocity on the heterogeneous reaction of SO2 over Fe2O3 - Yangyang Liu; Tao Wang; Qiuyue Ge; Zhuocheng Shi; Kejian Li; Kedong Gong; Lifang Xie; Wei Wang; Qianlong Wang; Jin Han; Hongbo Fu; Jianmin Chen; et al. (Atmospheric Environment, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Attenuated African swine fever virus through serial passaging of viruses in cell culture: a brief review on the knowledge gathered during 60 years of research - Xiaoyue Zhang; Zhenzhong Wang; Shengqiang Ge; Yuanyuan Zuo; Haodong Lu; Yan Lv; Naijun Han; Yumei Cai; Xiaodong Wu; Zhiliang Wang (Virus Genes, 2023)

Deep blue artificial intelligence for knowledge discovery of the intermediate ocean - Ge Chen; Baoxiang Huang; Jie Yang; Milena Radenkovic; Linyao Ge; Chuanchuan Cao; Xiaoyan Chen; Linghui Xia; Guiyan Han; Ying Ma (Frontiers in Marine Science, 2023)
Oceans at a depth ranging from ~100 to ~1000-m (defined as the intermediate water here), though poorly understood compared to the sea surface, is a critical layer of the Earth system where many important oceanographic processes take place. Advances in ocean observation and computer technology have allowed ocean science to enter the era of big data (to be precise, big data for the surface layer, small data for the bottom layer, and the intermediate layer sits in between) and greatly promoted our understanding of near-surface ocean phenomena. During the past few decades, however, the intermediate ocean is also undergoing profound changes because of global warming, the research and prediction of which are of intensive concern. Due to the lack of three-dimensional ocean theories and field observations, how to remotely sense the intermediate ocean from space becomes a very attractive but challenging scientific issue. With the rapid development of the next generation of information technology, artificial intelligence (AI) has built a new bridge from data science to marine science (called Deep Blue AI, DBAI), which acts as a powerful weapon to extend the paradigm of modern oceanography in the era of the metaverse. This review first introduces the basic prior knowledge of water movement in the ~100 m ocean and vertical stratification within the ~1000-m depths as well as the data resources provided by satellite remote sensing, field observation, and model reanalysis for DBAI. Then, three universal DBAI methodologies, namely, associative statistical, physically informed, and mathematically driven neural networks, are elucidated in the context of intermediate ocean remote sensing. Finally, the unique advantages and potentials of DBAI in data mining and knowledge discovery are demonstrated in a top-down way of “surface-to-interior” via several typical examples in physical and biological oceanography.

Coal-fired power plant CCUS project comprehensive benefit evaluation and forecasting model study - Jieping Han; Jiachun Li; Xi Tang; Lechen Wang; Xiaolong Yang; Zeqi Ge; Fei Yuan (Journal of Cleaner Production, 2023)

Performance analysis of a new thermal management for thermoelectric cooler - Jinwen Yang; Jitian Han; Xiaoxuan Zhu; Yi Ge; Wanchao Zhu (International Journal of Refrigeration, 2023)

Roles of microRNAs and exosomes in Helicobacter pylori associated gastric cancer - Xiao-Han Xu; Shu-Li Shao; Dong Guo; Li-Na Ge; Zan Wang; Peng Liu; Yuan-Yong Tao (Molecular Biology Reports, 2023)

Shift work and nonalcoholic fatty liver disease incidence among Chinese rail workers: a 4-year longitudinal cohort study - Jiahui Xu; Shu Ni; Yuming Wang; Mengfan Yan; Xueli Yang; Han Ge; Zizhuo Jia; Ze Yang; Anqi Shan; Huanyu Liu; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2023)

Assembling plant diversity mitigates greenhouse gas emissions and achieves high nitrogen removal when treating the low-C/N wastewater by constructed wetlands - Hang Jiang; Yuanyuan Du; Wenjuan Han; Lichunxiao Wang; Chenxu Xiang; Ying Ge; Jie Chang (Environmental Science and Pollution Research, 2023)

Inhibition of Spinal 5-HT3 Receptor and Spinal Dorsal Horn Neuronal Excitability Alleviates Hyperalgesia in a Rat Model of Parkinson’s Disease - Cheng-Jie Li; Li-Ge Zhang; Lu-Bing Liu; Meng-Qi An; Li-guo Dong; Han-Ying Gu; Yong-Ping Dai; Fen Wang; Cheng-Jie Mao; Chun-Feng Liu (Molecular Neurobiology, 2022)

Source and composition analysis of petroleum hydrocarbons in the refinery circulating water - Ge Ma; Han Xiao; Xinming Wei; Anshan Xiao; Xiaoying Sun; Xiang Gao (Environmental Science and Pollution Research, 2022)

Insight into different adsorption behaviors of two fluoroquinolone antibiotics by sediment aggregation fractions - Bo Zhang; Juan Chen; Chao Wang; Peifang Wang; Ge Cui; Jingjing Zhang; Yu Hu; Han Gao (Environmental Science and Pollution Research, 2022)

Double knock-in pig models with elements of binary Tet-On and phiC31 integrase systems for controllable and switchable gene expression - Qin Jin; Xiaoyu Yang; Shixue Gou; Xiaoyi Liu; Zhenpeng Zhuang; Yanhui Liang; Hui Shi; Jiayuan Huang; Han Wu; Yu Zhao; Zhen Ouyang; Quanjun Zhang; et al. (Science China Life Sciences, 2022)

Combination of bicarbonate and low temperature stress induces the biosynthesis of both arachidonic and docosahexaenoic acids in alkaliphilic microalgae Dunaliella salina HTBS - Zhile Guo; Yuyong Hou; Zhiyong Liu; Yanbo Ma; Tong Han; Nahui Hao; Yuanjiang Yao; Chunxuan Lan; Tongling Ge; Maliheh Safavi; Weijie Wang; Lei Zhao; et al. (Frontiers in Marine Science, 2022)
High bicarbonate levels and low temperature may have an impact on microalgae cultivation. However, changes in cellular composition in response to the combination of the above stresses are still poorly understood. In this study, the combined effects of bicarbonate and low temperature on biochemical changes in alkaliphilic microalgae Dunaliella salina HTBS were investigated. Comparing to the control condition of 25°C without bicarbonate, the cell density was increased from 0.69 to 1.18 in the treatment condition of 0.15 M bicarbonate and low temperature (16 °C) while the lipid\protein\carbohydrate contents were increased from 34.71% to 43.94%, 22.44% to 26.03%, 22.62% to 29.18%, respectively. Meanwhile, the PUFAs, arachidonic acid (AA) and docosahexaenoic acid (DHA) contents reached to 3.52% and 4.73% with the combination of low temperature and bicarbonate, respectively, whereas they were not detected when the cells were treated with single condition. Moreover, both the chlorophyll and carotenoid contents were also detected with increased profiles in the combined treatments. As a result, the maximum photochemical efficiency but not reduced non-photochemical quenching was strengthened, which enhanced the photosynthetic performance. Additionally, our results indicated that D. salina HTBS could acclimate to the combined stress by up-regulating the activity of SOD\CAT and reducing MDA content. These findings demonstrated that the addition of a certain bicarbonate under low temperature could effectively enhance the biomass production and accumulation of AA and DHA, which would benefit the development of the microalgae industry in value-added products.

Rootstock rescues watermelon from Fusarium wilt disease by shaping protective root-associated microbiomes and metabolites in continuous cropping soils - An-Hui Ge; Zhi-Huai Liang; Li-Li Han; Ji-Ling Xiao; Yi Zhang; Qing Zeng; Ji-Fang Xiang; Chao Xiong; Li-Mei Zhang (Plant and Soil, 2022)

Assessment of the inhalation exposure and incremental lifetime cancer risk of PM2.5 bounded polycyclic aromatic hydrocarbons (PAHs) by different toxic equivalent factors and occupancy probability, in the case of Xi’an - Yumeng Wang; Zedong Wang; Jingzhi Wang; Runyu Wang; Xinxin Ding; Neil McPherson Donahue; Zhibao Dong; Ge Ma; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2022)

Effect of light intensity on bound EPS characteristics of two Microcystis morphospecies: the role of bEPS in the proliferation of Microcystis - Xianzhe Wang; Xingye Han; Hongmei Ge (Journal of Oceanology and Limnology, 2022)

Household solid fuel use with diabetes and fasting blood glucose levels among middle-aged and older adults in China - Yuxiong Chen; Siqin Feng; Zhen’ge Chang; Yakun Zhao; Jia Fu; Yijie Liu; Siqi Tang; Yitao Han; Yanbo Liu; Yuanxun Zhang; Shuyang Zhang; Zhongjie Fan (Environmental Science and Pollution Research, 2022)

Putative role of corazonin in the ovarian development of the swimming crab Portunus trituberculatus - Shisheng Tu; Fuqiang Ge; Yaoyao Han; Mengen Wang; Xi Xie; Dongfa Zhu (Frontiers in Marine Science, 2022)
Corazonin (Crz) is a neuropeptide that widely distributed in insects and crustaceans. The Crz is proposed to have pleiotropic functions in insects, but its physiological roles in crustaceans are poorly understood. In the present study, Crz and its putative receptor ( CrzR ) were identified from the swimming crab, Portunus trituberculatus , and their interaction was validated using the Dual-Luciferase reporter assay system. Tissue distribution analysis showed the PtCrz was mainly derived from center nerve system, while its receptor was highly expressed in Y-organ, the main site for ecdysteroids synthesis. Exposure of YO to synthetic Crz and CrzR dsRNA respectively led to the transcriptional changes of two ecdysteroidogenesis genes, further indicating a putative role of Crz signaling on ecdysteroids synthesis. During the ovarian development, the mRNA levels of PtCrz and PtCrzR increased significantly in vitellogenic stages, suggesting a potential role of Crz signaling in vitellogenesis. The hypothesis was further strengthened by in vitro experiments that the expression of vitellogenin ( Vg ), Vg receptor ( VgR ), cyclinB , and Cdc2 in ovary explants could be induced by synthetic Crz, whereas reduced by CrzR dsRNA. In addition, since 20-hydroxyecdysone also showed a stimulating effect on Vg expression, an indirect regulation of Crz signaling on ovarian development via ecdysteroids might also exist.

Species identity but not richness affects effluent nitrogen, phosphorus, and potassium concentrations and the ratios in floating-constructed wetlands - Wenjuan Han; Yuanyuan Du; Chenxu Xiang; Yu Liu; Jie Chang; Ying Ge (Environmental Science and Pollution Research, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Satellite observed shape-based overall rotation—A new aspect in eddy kinematics - Xueqing Yang; Guiyan Han; Chunyong Ma; Chuanchuan Cao; Jie Yang; Ge Chen (Acta Oceanologica Sinica, 2022)

Phytoplankton Species Diversity Patterns and Associated Driving Factors in China’s Jiulong River Estuary: Roles That Nutrients and Nutrient Ratios Play - Feiyang Ge; Zhiyuan Ma; Bin Chen; Yu Wang; Xiaoqian Lu; Shenqun An; Dian Zhang; Wanting Zhang; Weiwei Yu; Wenxuan Han; Xingguang Yu; Zhenghua Liu; et al. (Frontiers in Marine Science, 2022)
Understanding diversity patterns and associated driving factors are the critical topics in macroecology and conservation biology. Phytoplankton are highly susceptible to environmental changes in estuaries, particularly eutrophication. This study examined phytoplankton alpha and beta diversity using investigation data in May (springtime), August (summer) and November (autumn) 2009 in China’s Jiulong River estuary, where it was easily polluted because of considerable discharge from a highly dense human population and low self-purification capacity with its limited river basin area, potentially resulting in eutrophication and then influencing phytoplankton diversity. Potential influencing factors were also explored, including dissolved oxygen, salinity, nutrients, nutrient ratios, geographic and hydrologic distance, and so on. The results indicated that Shannon’s index ( H’ ) and Pielou’s index ( J ) decreased from the estuary’s upper to middle and then increased from middle to lower reaches, Simpson’s ( D ) observed the opposite trend and species number ( S ) gradually increased from the estuary’s upper to lower reaches. For beta diversity, all the indices showed a gradual decrease trend from the estuary’s upper to lower reaches, where also, turnover dominated beta diversity for all seasons. It is noteworthy that the significant roles that nutrients and nutrient ratios played in shaping phytoplankton diversity patterns and the nutrient balance were characterized by excess nitrogen (N) and silicon (Si) and limited phosphorus (P), which could potentially cause diatom blooms. Findings also showed that decreasing Si concentrations can help to reduce overall pollution levels as well as the restoration of the estuary’s ecosystem better than just reducing N alone. Accordingly, this study advocates for the protection of the entire estuary system with particular emphasis on its upper reaches. Moreover, greater attention should also be paid to impacts associated with N input and nutrient ratio trade-offs to the prospective watershed management of this estuary. This study provides a practical approach to explore estuarine diversity in a comprehensive way, which can inform effective biodiversity conservation and also be applied to other marine ecosystems to better guide sustainable management and conservation practices.

Multivariate statistical analysis of potentially toxic elements in soils under different land uses: Spatial relationship, ecological risk assessment, and source identification - Yuejun He; Xiaoxiao Han; Jingsong Ge; Lingqing Wang (Environmental Geochemistry and Health, 2022)

Bacteria-based nanosystems for enhanced antitumor therapy - Yu Han; Miao Fan; Dandan Han; Kun Ge; Jin Chang; Jinchao Zhang (Science China Life Sciences, 2022)

Synthesis of Silver- and Strontium-Substituted Hydroxyapatite with Combined Osteogenic and Antibacterial Activities - Yunfei Li; Wenying Wang; Jing Han; Zirui Li; Qiuxiang Wang; Xue Lin; Kun Ge; Guoqiang Zhou (Biological Trace Element Research, 2022)

A Physics-Informed Neural Network for the Prediction of Unmanned Surface Vehicle Dynamics - Peng-Fei Xu; Chen-Bo Han; Hong-Xia Cheng; Chen Cheng; Tong Ge (Journal of Marine Science and Engineering, 2022)
A three-degrees-of-freedom model, including surge, sway and yaw motion, with differential thrusters is proposed to describe unmanned surface vehicle (USV) dynamics in this study. The experiment is carried out in the Qing Huai River and the data obtained from different zigzag trajectories are filtered by a Gaussian filtering method. A physics-informed neural network (PINN) is proposed to identify the dynamic models of the USV. PINNs combine the advantages of data-driven machine learning and physical models. They can also embed the speed and steering models into the loss function, which can significantly retain all types of information. Compared with traditional neural networks, the results show that the PINN has better generalization ability in predicting the surge and sway velocities and rotation speed with only limited training data.

Comparing the effects of plant diversity on the nitrogen removal and stability in floating and sand-based constructed wetlands under ammonium/nitrate ratio disturbance - Yuanyuan Du; Shaodan Niu; Hang Jiang; Bin Luo; Qian Wang; Wenjuan Han; Yu Liu; Jie Chang; Ying Ge (Environmental Science and Pollution Research, 2021)

Sources, Toxicity and Detection Techniques of Semicarbazide: A Review - Xiuhui Tian; Huanjun Li; Dianfeng Han; Fenggong Wen; Huan Liu; Ge Liu; Kaixiu Peng; Xianghong Gong; Xin Liu; Weiyun Wang; Haixia Yu; Yingjiang Xu (Journal of Ocean University of China, 2021)

An Eddy Perspective of Global Air-Sea Covariation - Jianjie Liu; Ge Chen; Guiyan Han; Bentao Zhang (Journal of Meteorological Research, 2021)

Genetic changes and evolutionary analysis of canine circovirus - Lin Wang; Yifan li; Zhiyuan Guo; Ying Yi; Han Zhang; Haikun Shangguan; Chengshi Huang; Junwei Ge (Archives of Virology, 2021)

Effects of different temperatures on seawater acclimation in rainbow trout Oncorhynchus mykiss: osmoregulation and branchial phospholipid fatty acid composition - Jian Ge; Ming Huang; Yangen Zhou; Chengyue Liu; Cui Han; Qinfeng Gao; Yunwei Dong; Shuanglin Dong (Journal of Comparative Physiology B, 2021)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Pairwise‐rotated EOFs of global cloud cover and their linkages to sea surface temperature - Yanrong Li; Jinming Ge; Zixiang Dong; Xiaoyu Hu; Xuan Yang; Meihua Wang; Zihang Han (International Journal of Climatology, 2021)
Sea surface temperature (SST) could significantly affect the dynamic and thermodynamic conditions of the atmospheric circulation and consequently the cloud variations. Here we use several different satellite records to extract the spatial‐time modes of total cloud cover (TCC) by employing a pairwise rotation of Empirical Orthogonal Function analysis. The results show that the first two principal oscillation modes of TCC are closely associated with the Central Pacific El Niño Southern Oscillation (CP ENSO) and Eastern Pacific (EP) ENSO during the 1980s–2000s, while the ENSO‐like mode of TCC can provide an evident contribution to the TCC change during the 2000s–2010s. In CP El Niño, the cloud vertical structure decomposed from CloudSat observations shows an increase of cloud occurrence frequency near the equator and around 40°, and a decrease around 10° in both hemispheres, suggesting a symmetric tightening of Hadley cell (HC). In addition, cloud occurrence frequency increases around 180°, which is accompanied by an eastward shift of Walker circulation (WC). In EP El Niño, TCC increases (decreases) over the Equatorial Eastern Pacific (Western Pacific warm pool), and decreases asymmetrically over the subtropical Pacific Ocean, indicating a weakening of WC and an asymmetric tightening of HC, respectively. The different responses of circulation and clouds to CP and EP El Niño highlight the nonlinearity of El Niño SST forcing. We also construct a trend mode of TCC to investigate cloud long‐term responses to SST warming by transferring the linear trends of the rest modes to a specific mode. The principal components (PCs) of TCC trend modes are strongly correlated with global‐mean SST (GSST) with correlation a coefficient of about 0.60 during the 1980s–2000s and 0.45 during the 2000s–2010s, suggesting a continued influence of global SST warming on TCC. The global TCC change is mainly influenced by the combined effects of Atlantic Multi‐decadal Oscillation (AMO), Pacific Decadal Oscillation (PDO) and Indian Ocean Dipole (IOD). The variation about the trend mode of TCC is closely associated with PDO and IOD.

Long-term study of heavy metal pollution in the northern Hangzhou Bay of China: temporal and spatial distribution, contamination evaluation, and potential ecological risk - Hao Xu; Huahong Yang; Qiyun Ge; Zhenyi Jiang; Yang Wu; Yamei Yu; Deming Han; Jinping Cheng (Environmental Science and Pollution Research, 2021)

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Increasing plant diversity offsets the influence of coarse sand on ecosystem services in microcosms of constructed wetlands - Yuanyuan Du; Bin Luo; Wenjuan Han; Yingyao Duan; Chenchen Yu; Meng Wang; Ying Ge; Jie Chang (Environmental Science and Pollution Research, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Illumina MiSeq sequencing and network analysis the distribution and co-occurrence of bacterioplankton in Danjiangkou Reservoir, China - Zhao-Jin Chen; Ge Xu; Chuan-Yu Ding; Bao-Hai Zheng; Yan Chen; Hui Han; Yu-Ying Li; Jian-Wei Shi; Lan-Qun Hu (Archives of Microbiology, 2020)

Towards More Snow Days in Summer since 2001 at the Great Wall Station, Antarctic Peninsula: The Role of the Amundsen Sea Low - Minghu Ding; Wei Han; Tong Zhang; Xiaoyuan Yue; Jeremy Fyke; Ge Liu; Cunde Xiao (Advances in Atmospheric Sciences, 2020)

Resolving rupture processes of great earthquakes: Reviews and perspective from fast response to joint inversion - Han Yue; Yong Zhang; Zengxi Ge; Teng Wang; Li Zhao (Science China Earth Sciences, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Difference in survival between right- versus left-sided colorectal neuroendocrine neoplasms - Ge-han Xu; Hua-wei Zou; Ashley B. Grossman (Journal of Zhejiang University-SCIENCE B, 2019)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Structure-activity relationships of novel dithiocarbamates containing α,β-unsaturated ketone fragment as potent anticancer agents - Yuanqiang Wang; Ridong Li; Han Zhang; Zhiyong Zhang; Xin Wang; Zemei Ge; Runtao Li (Medicinal Chemistry Research, 2019)

A protocol for isolation and identification and comparative characterization of primary osteoblasts from mouse and rat calvaria - Baoyan Liu; Yanqin Lu; Yong Wang; Luna Ge; Naixiang Zhai; Jinxiang Han (Cell and Tissue Banking, 2019)

Adsorption and Desorption of Carbendazim and Thiamethoxam in Five Different Agricultural Soils - Lingxi Han; Qiqing Ge; Jiajia Mei; Yanli Cui; Yongfei Xue; Yunlong Yu; Hua Fang (Bulletin of Environmental Contamination and Toxicology, 2019)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Silencing of miR156 confers enhanced resistance to brown planthopper in rice - Yafei Ge; Junyou Han; Guoxin Zhou; Yunmin Xu; Yue Ding; Min Shi; Changkui Guo; Gang Wu (Planta, 2018)

A new DDA model for kinematic analyses of rockslides on complex 3-D terrain - Hong Zhang; Shu-guang Liu; Wei Wang; Lu Zheng; Ying-bin Zhang; Yan-qiang Wu; Zheng Han; Yan-ge Li; Guang-qi Chen (Bulletin of Engineering Geology and the Environment, 2018)

Identification, expression analysis, and function evaluation of 42 tomato DEAD-box RNA helicase genes in growth development and stress response - Jing Cai; Xiaoqing Meng; Ge Li; Tingting Dong; Jian Sun; Tao Xu; Zongyun Li; Yonghua Han; Mingku Zhu (Acta Physiologiae Plantarum, 2018)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Neural correlates of increased risk-taking propensity in sleep-deprived people along with a changing risk level - Yu Lei; Lubin Wang; Pinhong Chen; Yanyan Li; Wei Han; Mingmei Ge; Liu Yang; Shanshan Chen; Wendong Hu; Xinhuai Wu; Zheng Yang (Brain Imaging and Behavior, 2017)

GhVLN4 is involved in cell elongation via regulation of actin organization - Fenni Lv; Mingya Han; Dongdong Ge; Hui Dong; Xiaotong Zhang; Lifeng Li; Peipei Zhang; Zhongqi Zhang; Jing Sun; Kang Liu; Youlu Yuan (Planta, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Responses of Dissimilatory Nitrate Reduction to Ammonium and Denitrification to Plant Presence, Plant Species and Species Richness in Simulated Vertical Flow Constructed Wetlands - Chong-Bang Zhang; Wen-Li Liu; Wen-Juan Han; Ming Guan; Jiang Wang; Shu-Yuan Liu; Ying Ge; Jie Chang (Wetlands, 2017)

Plant species diversity reduces N2O but not CH4 emissions from constructed wetlands under high nitrogen levels - Wenjuan Han; Mengmeng Shi; Jie Chang; Yuan Ren; Ronghua Xu; Chongbang Zhang; Ying Ge (Environmental Science and Pollution Research, 2017)

Signal sampling for efficient sparse representation of resting state FMRI data - Bao Ge; Milad Makkie; Jin Wang; Shijie Zhao; Xi Jiang; Xiang Li; Jinglei Lv; Shu Zhang; Wei Zhang; Junwei Han; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2016)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Discovery of the New Plant Growth-Regulating Compound LYXLF2 Based on Manipulating the Halogenase in Amycolatopsis orientalis - Li Xu; Ting Han; Mei Ge; Li Zhu; XiuPing Qian (Current Microbiology, 2016)

Novel insights into a retinoic-acid-induced cleft palate based on Rac1 regulation of the fibronectin arrangement - Qinghuang Tang; Liwen Li; Min-Jung Lee; Qing Ge; Jong-Min Lee; Han-Sung Jung (Cell and Tissue Research, 2016)

Research on strategy marine noise map based on i4ocean platform: Constructing flow and key approach - Baoxiang Huang; Ge Chen; Yong Han (Journal of Ocean University of China, 2016)

Passive-source multitaper-spectral method based low-frequency data reconstruction for active seismic sources - Pan Zhang; Li-Guo Han; Yan Zhou; Zhuo Xu; Qi-Xin Ge (Applied Geophysics, 2015)

The relationship between left ventricle myocardial performance index of healthy women and geographical factors - Xiao Han; Miao Ge; Jie Dong; Zixuan Wang; Jinwei He; Rongrong Yang (International Journal of Biometeorology, 2015)

Exploring the synergistic use of multi-scale image object metrics for land-use/land-cover mapping using an object-based approach - Ning Han; Huaqiang Du; Guomo Zhou; Xiaojun Xu; Hongli Ge; Lijuan Liu; Guolong Gao; Shaobo Sun (International Journal of Remote Sensing, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

One-step integration of multiple genes into the oleaginous yeast Yarrowia lipolytica - Shuliang Gao; Linna Han; Li Zhu; Mei Ge; Sheng Yang; Yu Jiang; Daijie Chen (Biotechnology Letters, 2014)

A bZIP transcription factor, LrbZIP1, is involved in Lilium regale Wilson defense responses against Fusarium oxysporum f. sp. lilii - Nannan Zhang; Diqiu Liu; Wei Zheng; Hua He; Bo Ji; Qing Han; Feng Ge; Chaoyin Chen (Genes & Genomics, 2014)

Cloning and expression of floral organ development-related genes in herbaceous peony (Paeonia lactiflora Pall.) - Jintao Ge; Daqiu Zhao; Chenxia Han; Jing Wang; Zhaojun Hao; Jun Tao (Molecular Biology Reports, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Distinct Promoters Affect Pyrroloquinoline Quinone Production in Recombinant Escherichia coli and Klebsiella pneumoniae - Jiguo Sun; Zengye Han; Xizhen Ge; Pingfang Tian (Current Microbiology, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

The PR10 gene family is highly expressed in Lilium regale Wilson during Fusarium oxysporum f. sp. lilii infection - Hua He; Diqiu Liu; Nannan Zhang; Wei Zheng; Qing Han; Bo Ji; Feng Ge; Chaoyin Chen (Genes & Genomics, 2014)

Microarray analysis of differentially expressed genes engaged in fruit development between table and wine grape - Xicheng Wang; Emrul Kayesh; Jian Han; Chonghuai Liu; Chen Wang; Changnian Song; Anjing Ge; Jinggui Fang (Molecular Biology Reports, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Object-based classification using SPOT-5 imagery for Moso bamboo forest mapping - Ning Han; Huaqiang Du; Guomo Zhou; Xiaoyan Sun; Hongli Ge; Xiaojun Xu (International Journal of Remote Sensing, 2014)

Methylovorus sp. MP688 exopolysaccharides contribute to oxidative defense and bacterial survival under adverse condition - Xin Ge; Wenxi Wang; Yuemei Han; Jianhua Wang; Xianghua Xiong; Weicai Zhang (World Journal of Microbiology and Biotechnology, 2013)

Effects of position within wheat field and adjacent habitats on the density and diversity of cereal aphids and their natural enemies - Zi-Hua Zhao; Cang Hui; Da-Han He; Feng Ge (BioControl, 2013)

A method to estimate concentrations of surface-level particulate matter using satellite-based aerosol optical thickness - JinHua Tao; MeiGen Zhang; LiangFu Chen; ZiFeng Wang; Lin Su; Cui Ge; Xiao Han; MingMin Zou (Science China Earth Sciences, 2013)

Overexpression of a Malus xiaojinensis Nas1 Gene Influences Flower Development and Tolerance to Iron Stress in Transgenic Tobacco - De-Guo Han; Guo-Hui Yang; Ke-Dong Xu; Qin Shao; Ze-Yuan Yu; Bing Wang; Qiu-Lai Ge; Yang Yu (Plant Molecular Biology Reporter, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

Resting State fMRI-guided Fiber Clustering: Methods and Applications - Bao Ge; Lei Guo; Tuo Zhang; Xintao Hu; Junwei Han; Tianming Liu (Neuroinformatics, 2013)

Compromised cerebrovascular modulation in chronic anxiety: evidence from cerebral blood flow velocity measured by transcranial Doppler sonography - Hong-Liang Zhang; Zhen-Ni Guo; Ge Yang; Le Yang; Ke Han; Jiang Wu; Yingqi Xing; Yi Yang (Neuroscience Bulletin, 2012)

Flower color diversity revealed by differential expression of flavonoid biosynthetic genes and flavonoid accumulation in herbaceous peony (Paeonia lactiflora Pall.) - Daqiu Zhao; Jun Tao; Chenxia Han; Jintao Ge (Molecular Biology Reports, 2012)

Construction of a linkage map for quantitative trait loci associated with economically important traits in creeping bentgrass (Agrostis stolonifera L.) - Tifu Zhang; Min Ge; Xiaoqing Ye; Suleiman S. Bughrara; Han Zhao (Euphytica, 2012)

Flavonol glycosides, nigelflavonosides A–F from the whole plant of Nigella glandulifera (Ranunculaceae) - Yi Zhang; Dandan Ge; Qiu Chen; Wei He; Lifeng Han; Hongyan Wei; Xiaoguang Jia; Tao Wang (Journal of Natural Medicines, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

(−)-Epigallocatechin-3-gallate inhibits the replication cycle of hepatitis C virus - Chao Chen; Hui Qiu; Jian Gong; Qing Liu; Han Xiao; Xin-Wen Chen; Bin-Lian Sun; Rong-Ge Yang (Archives of Virology, 2012)

Experimentally Validated Hemodynamics Simulations of Mechanical Heart Valves in Three Dimensions - Vinh-Tan Nguyen; Yee Han Kuan; Po-Yu Chen; Liang Ge; Fotis Sotiropoulos; Ajit P. Yoganathan; Hwa Liang Leo (Cardiovascular Engineering and Technology, 2012)

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Isomer-specific effects of conjugated linoleic acid on proliferative activity of cultured neural progenitor cells - Han Wang; Tianqing Liu; Jihui Wang; Yanli Qi; Dan Ge; Shui Guan (Molecular and Cellular Biochemistry, 2011)

Episode simulation of Asian dust storms with an air quality modeling system - Cui Ge; Meigen Zhang; Zhiwei Han; Yanju Liu (Advances in Atmospheric Sciences, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Histological responses of host and non-host plants to Hyaloperonospora parasitica - Hua Li; Xintian Ge; Shiue Han; Krishnapillai Sivasithamparam; Martin John Barbetti (European Journal of Plant Pathology, 2011)

Comparative features of colorectal and gastric cancers with microsatellite instability in Chinese patients - Yan-qin Huang; Ying Yuan; Wei-ting Ge; Han-guang Hu; Su-zhan Zhang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Efficacy and safety of drug-eluting stent implantation for the treatment of in-stent restenosis occurring within bare-metal stent and drug-eluting stent - Heng Ge; Qing Zhang; Wei Zhou; Qing He; Zhi-hua Han; Ben He (Journal of Zhejiang University-SCIENCE B, 2010)

Analysis of synonymous codon usage in the UL24 gene of duck enteritis virus - Renyong Jia; Anchun Cheng; Mingshu Wang; Hongyi Xin; Yufei Guo; Dekang Zhu; Xuefeng Qi; Lichan Zhao; Han Ge; Xiaoyue Chen (Virus Genes, 2009)

Structure, redox, pK a, spin. A golden tetrad for understanding metalloenzyme energetics and reaction pathways - Louis Noodleman; Wen-Ge Han (JBIC Journal of Biological Inorganic Chemistry, 2006)

A novel deletion in TNNI2 causes distal arthrogryposis in a large Chinese family with marked variability of expression - Miao Jiang; Xiuli Zhao; Weitian Han; Chaoying Bian; Xuefu Li; Ge Wang; Yang Ao; Yunqing Li; Dongxu Yi; Yang Zhe; Wilson H. Y. Lo; Xue Zhang; et al. (Human Genetics, 2006)

Adaptive filtering of continuous GPS results - L. Ge; H.-Y. Chen; S. Han; C. Rizos (Journal of Geodesy, 2000)

Multipath Mitigation of Continuous GPS Measurements Using an Adaptive Filter - Linlin Ge; Shaowei Han; Chris Rizos (GPS Solutions, 2000)